Valvuloplasty ring, valvuloplasty kit, and method for manufacturing valvuloplasty ring

By using a fabric or raw fabric layer impregnated with hydrogel and cross-linking it in the valvuloplasty ring, the problems of hemolysis and stress concentration after valvuloplasty were solved, and the softness and stability of the valvuloplasty ring were improved.

CN121175010APending Publication Date: 2025-12-19TEIJIN LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202480032328.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-08-09
Filing Date
2024-05-22
Publication Date
2025-12-19

AI Technical Summary

Technical Problem

In the prior art, there are problems such as hemolysis caused by the annuloplasty ring after valvuloplasty, and stability issues caused by the out-of-plane movement and stress concentration of the annuloplasty ring.

Method used

A first layer of fabric or raw fabric impregnated with hydrogel is used to cover the surface of the annular core, and a soft rubber layer is combined with it through radiation or chemical cross-linking treatment to form a valve forming ring.

Benefits of technology

It effectively inhibits hemolysis of the annuloplasty ring, increases the out-of-plane flexibility of the annuloplasty ring, reduces stress concentration, and improves stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121175010A_ABST
    Figure CN121175010A_ABST
Patent Text Reader

Abstract

The invention provides an annuloplasty ring capable of inhibiting hemolysis. The annuloplasty ring includes (1) an annular core and (2) a first layer that covers the surface of the core and includes a fabric or fabric impregnated with a hydrogel, and the hydrogel is irradiated and crosslinked.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a valve repair ring, a valve repair kit, and a method for manufacturing a valve repair ring. Background Technology

[0002] In recent years, with the aging population, the number of valvular disease treatments in the field of cardiovascular surgery has been increasing.

[0003] Heart valve disease refers to conditions where the valves fail to function properly. Specifically, this includes conditions such as stenosis (obstructing blood flow due to impaired valve movement) and insufficiency (causing blood regurgitation due to the valve's inability to close completely). Treatment for mitral valve diseases such as mitral regurgitation and mitral stenosis, or tricuspid valve diseases such as tricuspid stenosis and tricuspid regurgitation, typically involves valve replacement surgery (replacing the valve with an artificial one) or valvuloplasty (preserving the patient's valve while adjusting its shape). Currently, valvuloplasty is the most common treatment. Furthermore, valvuloplasty is also performed in cases with rheumatic diseases or infective endocarditis that have already undergone valve replacement surgery.

[0004] In valvuloplasty, after repairing the damaged parts of the valve and chordae tendineae, a valvuloplasty ring is used to prevent the valve annulus from expanding again. Moreover, this valvuloplasty ring is generally made of a metal core such as titanium, cobalt alloy, or nickel-titanium, and is made of silicone rubber and polyethylene terephthalate (PET) fabric on the outermost periphery (e.g., Patent Document 1, Patent Document 2).

[0005] Existing technical documents

[0006] Patent documents

[0007] Patent Document 1: Japanese Patent Publication No. 2018-519895

[0008] Patent Document 2: Japanese Patent Application Publication No. 4-503318

[0009] Non-patent literature

[0010] Non-patent literature 1: Jpn. J. Cardiovasc. Surg. 37: 151-154 (2008, Journal of HeartValve Disease, 2005) Summary of the Invention

[0011] As one of the issues in valve repair surgery, examples include mitral regurgitation jets impacting the valve repair annulus after valve repair surgery, causing hemolysis and requiring a second surgery. This is believed to be due to red blood cells colliding with the PET fabric and being exposed to shear stress.

[0012] To address the aforementioned issues, for example in clinical settings, methods have been studied to avoid hemolysis by wrapping the patient's own pericardium around the annuloplasty ring. However, this method prolongs the procedure by requiring the harvesting of the patient's pericardium, thus increasing the burden on both the patient and the physician (Non-Patent Literature 1). Therefore, it is desirable to develop an annuloplasty ring that can inhibit hemolysis.

[0013] The subject of this invention is to provide, for example, a valve-forming ring capable of inhibiting hemolysis.

[0014] The present invention was made to solve the above-mentioned problems and is constructed in the following manner.

[0015] <First Method>

[0016] [1] A valve forming ring, comprising: (1) an annular core, and (2) a first layer of fabric or raw fabric containing a hydrogel covering the surface of the core, wherein the hydrogel is cross-linked by irradiation.

[0017] [2] According to the valve forming ring of [1], there is a second layer containing rubber between the core and the first layer, and the ratio of the arithmetic mean roughness of the surface of the first layer that does not contact the core or the second layer to the arithmetic mean roughness of the back side of the first layer that contacts the core or the second layer is 0.01 to 0.40.

[0018] [3] According to the valve shaping ring of [1] or [2], wherein the first layer comprises an impregnation layer and a hydrogel layer composed of hydrogel, the impregnation layer comprising a fabric or fabric impregnated with hydrogel, and the ratio of the stress of the hydrogel in the hydrogel layer before water absorption treatment to the stress after water absorption treatment is 0.05 to 0.80, wherein the water absorption treatment refers to placing the hydrogel layer in a solution at 30°C to 50°C for 30 minutes to 90 minutes.

[0019] [4] A valve-forming ring according to any one of [1] to [3], wherein the hydrogel is gelatin or collagen.

[0020] [5] A valve-forming ring according to any one of [1] to [4], wherein the irradiation in the above-mentioned irradiation crosslinking is selected from at least one of X-ray irradiation, gamma-ray irradiation, electron beam irradiation, UV irradiation and plasma irradiation.

[0021] [6] A valve-forming ring according to any one of [1] to [5], wherein the irradiation in the above-mentioned irradiation crosslinking is electron beam irradiation.

[0022] [7] A valve forming ring according to any one of [1] to [6], wherein the fabric or greige fabric comprises polyester fibers.

[0023] [8] A valve-forming ring according to any one of [1] to [7], wherein the above-mentioned hydrogel is further chemically cross-linked.

[0024] [9] A valve shaping ring, comprising: (1) an annular core and (2) a first layer of fabric or raw fabric impregnated with hydrogel covering the surface of the core.

[0025]

[10] A valvuloplasty ring according to any one of [1] to [9], which is used to suppress hemolysis during valvuloplasty.

[0026]

[11] A valvuloplasty kit comprising a valvuloplasty ring as described in any one of [1] to

[10] , and a holder and / or a sizer.

[0027]

[12] A method for manufacturing a valve-forming ring, the valve-forming ring comprising: (1) an annular core and (2) a first layer of fabric or raw fabric containing a hydrogel covering the surface of the core, the method comprising a step of irradiating the valve-forming ring with radiation.

[0028]

[13] According to the method of

[12] , the above-mentioned irradiation process is an irradiation process selected from at least one of X-rays, gamma rays, electron beams, UV and plasma.

[0029]

[14] According to the method described in

[12] or

[13] , wherein the above-mentioned process of irradiating radiation is a process of irradiating an electron beam.

[0030]

[15] The method according to any one of

[12] to

[14] , wherein the step of adding a crosslinking agent is further included.

[0031] <Second Method>

[0032] The present invention also includes the second aspect shown below.

[0033] [1] A valve shaping ring includes (1) an annular core and (2) a first layer of fabric or raw fabric containing hydrogel covering the surface of the core.

[0034] [2] According to the valve forming ring of [1], there is a second layer containing rubber between the core and the first layer.

[0035] [3] The valve-forming ring according to claim 1, wherein the hydrogel is gelatin or collagen.

[0036] [4] A valve forming ring according to any one of [1] to [3], wherein the fabric or greige fabric comprises polyester fibers.

[0037] [5] A valve-forming ring according to any one of [1] to [4], wherein the above-mentioned hydrogel is chemically cross-linked.

[0038] [6] A valve-forming ring according to any one of [1] to [5], wherein the crosslinking agent in the above chemical crosslinking is glutaraldehyde or glyoxal.

[0039] [7] A valve-forming ring according to any one of [1] to [6], wherein the ratio of the arithmetic mean roughness of the surface of the first layer that does not contact the core or the second layer to the arithmetic mean roughness of the back surface of the first layer that contacts the core or the second layer is 0.01 to 0.40.

[0040] [8] A valve-forming ring according to any one of [1] to [7], wherein the value of the above ratio is 0.02 to 0.25.

[0041] [9] A valve-forming ring according to any one of [1] to [8], wherein the value of the above ratio is 0.03 to 0.2.

[0042]

[10] A valvuloplasty kit comprising a valvuloplasty ring as described in any one of [1] to [9], and a ring holder and / or a ring measuring device.

[0043]

[11] A method for manufacturing a valve-forming ring, the valve-forming ring comprising (1) an annular core and (2) a first layer of fabric or raw fabric impregnated with hydrogel covering the surface of the core, the method comprising the following steps:

[0044] (Step 1) A composite of the annular core and the fabric or greige fabric is obtained by placing fabric or greige fabric on the outside of the annular core.

[0045] (Step 2) By contacting the above composite with the hydrogel, an impregnated composite containing the hydrogel is obtained.

[0046] (Step 3) Contact the above impregnated composite with the crosslinking agent.

[0047]

[12] According to the method described in

[11] , wherein the hydrogel is gelatin or collagen.

[0048]

[13] According to the method of

[11] or

[12] , wherein step 2 is performed by fixing the composite on the central axis of a generally cylindrical or generally prismatic container containing hydrogel.

[0049]

[14] The crosslinking agent is glutaraldehyde or glyoxal, and the method described in any one of

[11] to

[13] .

[0050]

[15] The method according to any one of

[11] to

[14] , wherein the concentration of the crosslinking agent is 0.01% to 0.7%.

[0051]

[16] The method according to any one of

[11] to

[14] , wherein the concentration of the crosslinking agent is 0.04% to 0.6%.

[0052] The following explains the issues related to the second method described above. Specifically, the annuloplasty ring uses a rigid metal core as a constituent element, which sometimes excessively restricts the movement of the annuloplasty ring due to pressure on the core. In this case, there are concerns about valvular stenosis and blood flow disruption. To avoid these situations, an annuloplasty ring that can conform to the out-of-plane movement of the annuloplasty ring (i.e., has flexibility in the out-of-plane direction of the annuloplasty ring) is needed.

[0053] To address the aforementioned issues, a valve-forming ring was proposed that adapts to the movement of the valve ring by adjusting the material and cross-sectional shape of the metal core. However, these valve-forming rings do not adequately adapt to the large movements of the valve in both contraction and expansion states, and there are concerns about a decrease in metal fatigue strength accompanying changes in cross-sectional shape.

[0054] Therefore, it is desirable to develop a valve repair ring capable of conforming to out-of-plane movements. As a related issue to the second approach, a valve repair ring with out-of-plane flexibility is provided. Furthermore, as an effect of the second approach, an example of providing a valve repair ring with out-of-plane flexibility can be cited.

[0055] <Third Method>

[0056] The present invention also includes the third aspect shown below.

[0057] [1] A valve-forming ring, comprising: (1) an annular core, and (2) a first layer covering the surface of the core circumferentially.

[0058] The first layer includes: an impregnation layer comprising a fabric or greige fabric impregnated with hydrogel, and a hydrogel layer composed of hydrogel.

[0059] [2] According to the valve forming ring of [1], there is a second layer containing rubber between the core and the first layer.

[0060] [3] The valve-forming ring according to [1] or [2], wherein the hydrogel is gelatin or collagen.

[0061] [4] A valve forming ring according to any one of [1] to [3], wherein the fabric or greige fabric comprises polyester fibers.

[0062] [5] A valve-forming ring according to any one of [1] to [4], wherein the above-mentioned hydrogel is chemically cross-linked.

[0063] [6] A valve-forming ring according to any one of [1] to [5], wherein the crosslinking agent in the above chemical crosslinking is glutaraldehyde or glyoxal.

[0064] [7] A valve-forming ring according to any one of [1] to [6], wherein the ratio of the stress before water absorption treatment of the hydrogel in the hydrogel layer to the stress after water absorption treatment of the hydrogel is 0.05 to 0.80, wherein the water absorption treatment refers to placing the hydrogel layer in a solution at 30°C to 50°C for 30 minutes to 90 minutes.

[0065] [8] A valve-forming ring according to any one of [1] to [7], wherein the value of the above ratio is 0.07 to 0.60.

[0066] [9] A valve-forming ring according to any one of [1] to [8], wherein the value of the above ratio is 0.07 to 0.50.

[0067]

[10] A valvuloplasty kit comprising a valvuloplasty ring as described in any one of [1] to [9], and a ring holder and / or a ring measuring device.

[0068] The following describes the issues related to the third method described above. Specifically, in valvuloplasty, after repairing the damaged parts of the valve and chordae tendineae, a valvuloplasty ring is used. Furthermore, examples of such valvuloplasty rings include those with a rigid metal core (e.g., titanium, cobalt alloy, nickel-titanium) at its center, made of silicone rubber and a polyethylene terephthalate (PET) fabric at its outermost periphery (e.g., Patent Document 1, Patent Document 2, US Patent No. 6805711), and artificial valve rings that may include, as part of their constituent elements, a sheet composed of a filament made of bio-absorbent material and hydrogel (Japanese Patent No. 6310167).

[0069] Valve annuloplasty rings, such as those described in Patent Document 1, Patent Document 2, and US Patent No. 6805711, suffer from stability issues. Specifically, these annuloplasty rings employ a rigid metal core as a constituent element, but due to repeated stress application, stress concentration areas may fail due to fatigue (e.g., metal fatigue).

[0070] It should be noted that Japanese Patent No. 6310167 primarily relates to a sheet composed of a filament made of bio-absorbent material combined with hydrogel, and only describes the possibility of its application to artificial valve annulus. That is, it does not mention the specific structure of the annulus, and of course, it does not address the problems mentioned above. Therefore, even if only the sheet of Patent No. 6310167 is applied to an annulus, the problems described above will still occur.

[0071] Therefore, there is a need to develop valvuloplasty rings that can overcome stability problems, such as those capable of suppressing stress concentration. As a related issue to the third approach, it is to provide a valvuloplasty ring capable of suppressing stress concentration (i.e., thereby reducing the possibility of damage caused by stress concentration). Furthermore, as an effect of the third approach, for example, it is possible to provide a valvuloplasty ring that reduces the possibility of damage caused by stress concentration.

[0072] The valve-forming ring according to the invention, for example, can inhibit hemolysis. Attached Figure Description

[0073] Figure 1 This is a diagram showing the appearance of the valve repair ring.

[0074] Figure 2 This is a diagram showing the layered structure of the valve-forming ring.

[0075] Figure 3 It is a diagram used to illustrate the flexibility in the out-of-plane and in-plane directions within the valve-forming ring.

[0076] Figure 4 This is a diagram illustrating a general description of an in-plane tensile test used in calculating von Mises stress.

[0077] Figure 5 This is a diagram used to illustrate the radius of curvature in the core of the valve repair ring. Detailed Implementation

[0078] <Valveolithic ring of the first aspect of the present invention>

[0079] The valve-forming ring of the first aspect of the present invention is characterized in that it comprises (1) an annular core and (2) a first layer of fabric or raw fabric impregnated with hydrogel covering the surface of the core, wherein the hydrogel is cross-linked by irradiation. Hereinafter, the valve-forming ring of the first aspect of the present invention will be described in detail.

[0080] As described above, the annuloplasty ring is used in valvuloplasty procedures performed for mitral valve diseases such as mitral regurgitation and mitral stenosis, or tricuspid valve diseases such as tricuspid stenosis and tricuspid regurgitation, to prevent postoperative annular re-enlargement. The annuloplasty ring is sometimes also referred to as an annular ring, artificial annular ring, annular band, or valve band. The annuloplasty ring of the present invention is, for example, as shown below... Figure 1 The appearance shown. Figure 1 The number 1 in the diagram corresponds to the valve repair ring of the present invention. Furthermore, the valve repair ring of the present invention, for example, as described below, includes the core, the first layer, and the second layer of the present invention, and their positional relationship is shown in the diagram. Figure 2 . Figure 2 The cross-sectional structure of the valve shaping ring of the present invention is shown, and the core 2, the first layer 4, and the second layer 3 of the present invention are disclosed.

[0081] The valve-forming ring of the present invention is suitable for implantation in, for example, the mitral valve annulus and the tricuspid valve annulus. Therefore, the valve-forming ring of the present invention is preferably shaped to approximate the outer shape of the mitral or tricuspid valve annulus. Specifically, its shape can be a complete ring surrounding the entire circumference of the valve annulus (also called a full ring), or a partial ring with a notch on a portion of the valve annulus. More specifically, examples include elliptical, C-shaped, D-shaped, kidney-shaped, bean-shaped, and oval shapes. It should be noted that the rigid and semi-rigid valve-forming rings described later are generally kidney-shaped or D-shaped in a manner conforming to the edge shape of the mitral valve annulus (e.g., see Japanese Patent Application Publication No. 2018-519986). Furthermore, the valve-forming ring of the present invention can be bilaterally symmetrical or asymmetrical. The valve-forming ring of the present invention is preferably flat or saddle-shaped. In particular, the saddle-shaped annulus, compared to a flat annulus, better reflects the inherent anatomical structure of the mitral valve annulus. Therefore, it can be a natural annulus shape, distributing the load on the annulus and minimizing the load transmitted to the valve tip and chordae tendineae. Furthermore, the valve-forming annulus of the present invention can be a flexible annulus, a rigid annulus, or a semi-rigid annulus, preferably a semi-rigid annulus. This is because a flexible annulus might be too soft and unable to adequately reshape the annulus, while a rigid annulus might not be able to conform to the movement of the annulus. Therefore, a semi-rigid annulus, possessing both flexibility and rigidity, is the most ideal design.

[0082] For example, by shaping the valve annuloplasty ring of the present invention as described above, the anteroposterior diameter of the valve annulus can be reduced, and the contact area between the anterior and posterior apexes can be increased. This effectively prevents re-enlargement of the valve annulus, prevents tissue damage at the valve apex contact line, and also helps prevent recurrence of mitral regurgitation. Furthermore, since the suture separation that causes postoperative mitral regurgitation is more likely to occur near the valve annulus relative to the left ventricular side of the valve apex, valve annulus formation based on the valve annuloplasty ring also strengthens the sutures near the valve annulus. Additionally, since the mitral valve annulus is continuously corrected to its normal annulus shape during systole, the effect of preventing recurrence of mitral regurgitation through remodeling can also be expected.

[0083] [Core portion of the first embodiment of the present invention]

[0084] The core of the first embodiment of the present invention is a core that shapes the valve-forming ring of the present invention, which is capable of surrounding the mitral valve annulus, tricuspid valve annulus, etc. The core of the first embodiment of the present invention takes a ring shape; specifically, it takes a shape corresponding to the shape of the valve-forming ring of the present invention described above. Furthermore, examples of the cross-sectional shape of the core of the first embodiment of the present invention include circular, square, and layered structures.

[0085] As a material for the core in the first aspect of the present invention, examples include metals, specifically nitinol (sometimes called nickel-titanium, titanium-nickel alloy), ELGILOY (sometimes called cobalt-chromium-nickel alloy), alloys with nickel, cobalt, chromium and molybdenum as the main components, stainless steel, etc. Among these, semi-rigid types of nitinol, ELGILOY or stainless steel that possess both flexibility and rigidity as described above are preferred. More preferably, superelastic materials such as nitinol or similar superelastic alloys are preferred. Here, superelasticity (sometimes called pseudoelasticity) refers to the elastic (reversible) response to applied stress caused by the phase transformation between the austenitic and martensitic phases of the crystal. Superelasticity enables the material to bend beyond what was previously expected with certain types of materials such as metal alloys (see U.S. Patent No. 11,554,015).

[0086] It should be noted that although the core of the first embodiment of the present invention is made of the aforementioned metal, it may also be partially flexible. For example, this can be adjusted by changing the number of layers in the core of that portion, changing the thickness of at least one core cross-section in that portion, inserting at least one core material having different materials, or arbitrarily combining them. Additionally, this can be adjusted by inserting spacers (e.g., polymer spacers and / or elastomeric spacers) between at least a pair of adjacent core layers. Furthermore, as another embodiment, a braided core composed of multiple wires, strands, and / or cords can be cited (e.g., see Japanese Patent Publication No. 2018-519986).

[0087] The size of the core, as a first aspect of the present invention, can be appropriately set according to the patient using the valve repair ring of the present invention. When its cross-section is circular, for example, the diameter is 300 micrometers to 1500 micrometers; when its cross-section is square (e.g., rectangular), for example, the width is 300 micrometers to 1500 micrometers and the height is 300 micrometers to 1500 micrometers. Furthermore, when it is a layered structure, for example, it has a structure consisting of 2 to 8 sheets of plates with a width of 300 micrometers to 3000 micrometers and a height of 30 micrometers to 1000 micrometers.

[0088] The core of the first embodiment of the present invention may have a predetermined radius of curvature. Specifically, for example, as... Figure 5 As shown, the core may have a first radius of curvature R represented by the rear tip R and / or a front tip r of the core. Specifically, the value of the radius of curvature R is, for example, 12 to 30, and the value of the radius of curvature r is, for example, 0.5 to 65.

[0089] It should be noted that the above-mentioned method for calculating the radius of curvature can refer to methods commonly known in the field. Alternatively, it can be calculated by referring to, for example, US2023 / 0125047. Furthermore, the terms "rear tip" and "front tip" are used as they are understood in the field.

[0090] [First layer of the first aspect of the present invention]

[0091] The first layer of the first embodiment of the present invention covers the surface of the core of the first embodiment of the present invention, comprising a fabric or greige fabric impregnated with hydrogel, and the hydrogel is crosslinked by irradiation.

[0092] In the first embodiment of the present invention, the first layer of the greige fabric or cloth is covered over the surface of the core of the first embodiment of the present invention. This coverage may be a portion of the core or the entirety of the core. As the fabric or greige fabric, a biocompatible fabric or greige fabric is preferred; specifically, examples include biocompatible knitted fabrics and woven fabrics. As the knitted fabric, various warp and weft knitting structures can be used. Particularly preferred knitted fabrics include double-layer Raschel knitted fabrics, plain knitted fabrics, rubber knitted fabrics, Tricot fabrics, and Raschel fabrics. For example, warp-knitted fabrics (in the undigested state of bioabsorbable materials) preferably have a density of 20 rows / inch to 200 rows / inch and 20 rows / inch to 55 rows / inch. From the viewpoints of ease of sewing between the greige fabric and biological tissue, water resistance, needle hole leakage, and anisotropy of warp-knitted fabrics, a ratio of 70 rows / inch to 110 rows / inch and 30 rows / inch to 45 rows / inch is preferred, and a ratio of 80 rows / inch to 100 rows / inch and 32 rows / inch to 42 rows / inch is even more preferred. Plain weave, twill weave, and satin weave can be used as the fabric.

[0093] In the first embodiment of the present invention, the fabric or greige fabric in the first layer is preferably composed of yarn made of bio-absorbent materials and / or non-bio-absorbent materials.

[0094] As for the wires made of bioabsorbable materials, there are no particular limitations as long as they are biocompatible and decompose or disappear within the body over time. Specifically, examples include polyglycolic acid, polylactic acid, poly(lactic-co-propylene) copolymer, polycyclic aromatic hydrocarbons (PAHs), polydioxanone, polycaprolactone, polyhydroxyalkanoates, modified polyvinyl alcohol, casein, modified starch, poly(lactic-co-propylene) copolymer, polyglycolic acid-lactic acid copolymer, and their derivatives. Preferably, at least one material selected from polylactic acid, polydioxanone, polyglycolic acid, poly(lactic-co-propylene) copolymer, and polyglycolic acid-lactic acid copolymer is used. In this case, versatility and strength are excellent, and it can be effectively decomposed and absorbed within the body.

[0095] As a non-biological absorbent material, there are no particular limitations as long as it is biocompatible and does not decompose or disappear within the body over time. Specifically, examples include fluoropolymers, nylon fibers, polyethylene terephthalate, polyethylene terephthalate, polybutylene terephthalate, polylactic acid, stereopolymer polylactic acid, polyester fibers copolymerized with the third component, acrylic fibers, vinylon fibers, vinylon chloride fibers, polyvinyl chloride fibers, polyethylene fibers, polypropylene fibers, polyurethane fibers, carbon fibers, polystyrene fibers, and polymethyl methacrylate. Preferably, at least one type selected from fluoropolymers, nylon fibers, polyester fibers, and polypropylene fibers is used. In this case, versatility and strength are excellent, maintaining sufficient strength for use as a fabric or greige fabric.

[0096] For the aforementioned non-bioabsorbable material used to make the thread, the total fineness is preferably 22 dtex to 110 dtex, the single filament fineness is preferably 0.8 dtex to 5.0 dtex, and the single filament count is preferably 1 to 48. By adjusting the thread to the above range, it is lightweight while maintaining sufficient strength within the above range. More preferably, the total fineness is 25 dtex to 50 dtex, the single filament fineness is preferably 1 dtex to 5 dtex, and the single filament count is preferably 5 to 20.

[0097] The aforementioned bioabsorbable material is preferably composed of a total fineness of 20 dtex to 200 dtex, a single filament fineness of 1.3 dtex to 44 dtex, and a single filament count of 1 to 24. By adjusting the material within these ranges, it can be decomposed and absorbed within the body. More preferably, the total fineness is 25 dtex to 50 dtex, the single filament fineness is preferably 1 dtex to 5 dtex, and the single filament count is preferably 5 to 20.

[0098] The aforementioned bio-absorbent materials and / or non-bio-absorbent materials used to make threads can be monofilaments or multifilaments. When multifilaments are used, they exhibit a soft texture. Furthermore, when used in vivo, multifilaments allow cells and tissues to easily penetrate between the monofilaments, making them preferable for tissue regeneration. On the other hand, monofilament threads have higher cleaning efficiency compared to multifilaments. When the threads made of bio-absorbent materials and / or non-bio-absorbent materials are multifilaments, the number of monofilaments is 5 to 20, and the total fineness is preferably 25 dtex to 50 dtex.

[0099] In the first embodiment of the present invention, the fabric or greige fabric in the first layer is impregnated with a hydrogel. Specifically, examples of such hydrogels include gelatin, collagen, polyvinyl alcohol, polyacrylamide, poly-N-vinylpyrrolidone, polyhydroxyethyl methacrylate, polyethylene oxide, polyethylene glycol, polyethylene glycol monomethyl ether, cellulose, polyacrylate, polymethyl methacrylate, polylactic acid, polyvinylsulfonic acid, polyamide, poly(L-lysine), hydrophilic polyurethane, maleic anhydride polymers, proteins, fibroin, collagen, cellulose polymers, methylcellulose, carboxymethylcellulose, dextran, carboxymethyl dextran, modified dextran, alginate, alginic acid, pectic acid, hyaluronic acid, chitin, pullulan, elastin, laminin, agarose, gellan gum, chitosan, carboxymethyl starch, chondroitin sulfate, guar gum, starch, and substances comprising copolymers, mixtures, and derivatives thereof. Gelatin or collagen is preferred, with gelatin being more preferred.

[0100] As for the aforementioned gelatin, its raw materials can be, for example, obtained by unwinding the triple helix of collagen from bovine bone, bovine hide, pigskin, bird, or fish into a single molecular chain. The manufacturing methods for the aforementioned gelatin raw materials include acid treatment, alkali treatment (or lime treatment), etc., and the raw materials can be gelatin manufactured by any of these methods, or commercially available gelatin raw materials. Furthermore, commercially available gelatin raw materials undergo various purification processes during their manufacturing process up to extraction, thus containing fewer components other than protein. Generally, they typically have a composition of 85% or more protein, 8-14% moisture, less than 2% ash, and less than 1% other components (lipids, polysaccharides, etc.). In this invention, the aforementioned general gelatin raw materials can also be used.

[0101] Gelatin raw materials are thermally modified collagen, so their amino acid composition is almost identical to collagen, quite different from other proteins. Glycine accounts for about one-third of the total, and the amino acid sequence is repeated once for every three amino acids. One method to distinguish between collagen and gelatin is, for example, by observing the 31.5-degree signal obtained from wide-angle X-ray measurement. This 31.5-degree signal originates from the triple helix structure of collagen; if the triple helix structure of collagen unwinds to form gelatin, this signal disappears.

[0102] The content of gelatin raw material in the gelatin solution is preferably 1% to 70% by weight, more preferably 3% to 20% by weight.

[0103] Water is used as the solvent to dissolve gelatin raw materials. Polyols, dimethyl sulfoxide, etc. can be added as needed to adjust the viscosity.

[0104] As a method for impregnating the first layer of fabric or greige fabric with hydrogel according to the first aspect of the present invention, it can be carried out using methods commonly practiced in the art. Specifically, for example, methods such as spraying or coating the hydrogel onto the fabric or greige fabric can be cited. More specifically, it is carried out by "impregnating the fabric or greige fabric with a solution containing hydrogel (e.g., Nitta gelatin; beMatrix Gelatin LS-H), and repeatedly cooling or drying it at a specified temperature." The temperature of the hydrogel solution in the above method is, for example, 20°C to 80°C, and the impregnation time is, for example, a few seconds to a few minutes. In addition, the cooling or drying time after impregnation is, for example, 2 minutes to 24 hours.

[0105] Additionally, for example, when the hydrogel is a protein, the coating amount (mass of solid component per unit area) of the hydrogel on the fabric or greige fabric is typically 1 mg / cm². 2 ~200mg / cm 2 Preferably 1 mg / cm 2 ~100mg / cm 2 More preferably 2 mg / cm 2 ~80mg / cm 2 More preferably 2–60 mg / cm³ 2 .

[0106] In the first layer of the fabric or greige fabric of the first embodiment of the present invention, the hydrogel is cross-linked by irradiation. "The hydrogel is cross-linked by irradiation" means that the hydrogel is cross-linked by radiation irradiation, as described later.

[0107] Examples of radiation irradiation used in the aforementioned crosslinking process include X-ray irradiation, gamma-ray irradiation, electron beam irradiation, UV irradiation, and plasma irradiation. From the viewpoint of hemolysis rate, electron beam irradiation is preferred. Furthermore, the radiation irradiation in the aforementioned crosslinking process can use only one type of radiation, or it can combine various types of radiation. As a specific example of combining multiple types, for instance, as the first irradiation, irradiation can produce radiation with a low degree of crosslinking (e.g., UV irradiation), followed by a second irradiation producing radiation with a high degree of crosslinking (e.g., electron beam irradiation). By employing this method, a valve-forming ring with higher strength can be obtained.

[0108] As for the irradiation conditions for the above-mentioned cross-linking process, the accelerating voltage is preferably 10 kV to 8000 kV, and the irradiation dose is preferably 5 kGy to 200 kGy, more preferably 10 kGy to 60 kGy, and even more preferably 20 to 40 kGy. The irradiation time can be adjusted appropriately. The temperature during irradiation is typically -80°C to 40°C and can be adjusted appropriately. Furthermore, irradiation can be carried out in the presence of a desiccant and a deoxidizer, thereby suppressing ozone production and inhibiting the deactivation of oxygen in the free radical atmosphere generated by electron beam irradiation.

[0109] It should be noted that any method commonly used in this field for irradiating the aforementioned radiation is acceptable (e.g., see Japanese Patent Application Publication No. 2020-157516, Japanese Patent Application Publication No. 2021-146242, etc.). For example, irradiating the first layer of the first embodiment of the present invention, which contains hydrogel, with radiation is sufficient, and the following conditions may apply. The following are merely examples and are not intended to limit the scope of the invention.

[0110] Irradiation device: Electron beam irradiation device (e.g., RDI; high-frequency, high-voltage electron accelerator).

[0111] Radiation dosing apparatus: CTA radiation dosimeter apparatus (e.g., Shimadzu UV1800 spectrophotometer).

[0112] Radiation meter: CTA radiation meter (e.g., Fujifilm FTR-125).

[0113] Accelerating voltage: 4.8 megavolts

[0114] Current: 20 mA

[0115] Vehicle speed (outer perimeter): 18.0 m / min

[0116] Radiation dose: 30 kGy

[0117] Irradiation direction: single-sided

[0118] Number of irradiations: 2

[0119] Supporting material: laminated corrugated paper

[0120] The degree of crosslinking (degree of decomposition, rate of decomposition) of the irradiated crosslinked hydrogel described above can be evaluated using, for example, absorbance before and after radiation irradiation. This is because the absorbance increases as hydrogel decomposition occurs, a phenomenon commonly observed in this field. Specifically, the absorbance at complete hydrogel decomposition and after a certain time are measured, and the hydrogel's decomposability is calculated from their ratio. Then, based on this, the decomposition rate of the hydrogel before radiation irradiation and the decomposition rate of the hydrogel after radiation irradiation are calculated, and their ratio (decomposition rate of the hydrogel after radiation irradiation / decomposition rate of the hydrogel before radiation irradiation) is calculated.

[0121] In the valve-forming ring of the first embodiment of the present invention, as described above, the irradiated cross-linked hydrogel is used as one of the constituent elements. Surprisingly, by employing the above-described configuration, hemolysis can be suppressed. This is also made clear from the description of the embodiments described later.

[0122] In the first layer of fabric or greige fabric of the first embodiment of the present invention, the hydrogel may be further chemically crosslinked. "The hydrogel may be chemically crosslinked" means that the hydrogel is crosslinked by a crosslinking agent described later.

[0123] Examples of crosslinking agents used in the aforementioned chemical crosslinking include aldehyde-based crosslinking agents (glutaraldehyde, formaldehyde, glyoxal, etc.), isocyanate-based crosslinking agents (hexamethylene diisocyanate, etc.), carbodiimide-based crosslinking agents (1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride, etc.), polyepoxy-based crosslinking agents (ethylene glycol diethyl ether, etc.), and transglutaminase, etc. Aldehyde-based crosslinking agents are preferred, glutaraldehyde or glyoxal are more preferred, and glutaraldehyde is particularly preferred.

[0124] As a method for chemically crosslinking the hydrogel in the fabric or greige fabric of the first layer of the first embodiment of the present invention, any method commonly performed in the field is acceptable. For example, simply impregnating the first layer of the present invention, which contains the hydrogel, with a solution containing a crosslinking agent (e.g., Tokyo Chemical Industry Co., Ltd.; 50% glutaraldehyde solution). The reaction time for impregnation with the solution containing the crosslinking agent is typically 30 minutes to 24 hours, and can be adjusted appropriately. Furthermore, the impregnation temperature is typically 0°C to 50°C, and can be adjusted appropriately. Additionally, the concentration of the crosslinking agent in the above-mentioned chemical crosslinking is typically 0.01% by mass to 10% by mass.

[0125] The thickness of the first layer, as a first aspect of the present invention, can be appropriately set according to the patient using the valve annuloplasty ring of the present invention, for example, 100 micrometers to 2000 micrometers, preferably 150 micrometers to 1700 micrometers, and more preferably 200 micrometers to 1500 micrometers.

[0126] In addition to the core and first layer of the first embodiment of the present invention described above, the valve-forming ring of the present invention may also include a second layer containing rubber (hereinafter sometimes abbreviated as the second layer of the first embodiment of the present invention). The second layer of the first embodiment of the present invention contains rubber, which will be described later, and is located between the core of the first embodiment of the present invention and the first layer of the first embodiment of the present invention.

[0127] Examples of rubber used in the second layer of the first embodiment of the present invention include silicone rubber, latex rubber, synthetic rubbers such as styrene-butadiene-styrene (SBS), styrene-isoprene-styrene (SIS), styrene-ethylene-butene-styrene (SEBS), and styrene-ethylene-propylene-styrene (SEPS), fluorinated silicone rubber, fluororubber, chloroprene rubber, nitrile rubber, acrylic rubber, epichlorohydrin rubber, isoprene rubber, styrene-butadiene rubber, butadiene rubber, ethylene-propylene rubber, chlorinated polyethylene rubber, chlorosulfonated polyethylene rubber, and butyl rubber. Silicone rubber is preferred. Furthermore, the above-mentioned rubbers can also be sewn together with stitching thread.

[0128] The thickness of the second layer, which is the first aspect of the present invention, can be appropriately set according to the patient using the valve repair ring of the first aspect of the present invention, for example, from 50 micrometers to 1500 micrometers.

[0129] In the valve-forming ring of the first embodiment of the present invention, it may also be configured such that: "a second layer containing rubber exists between the core and the first layer (3), and the ratio of the arithmetic mean roughness of the surface of the first layer that does not contact the core or the second layer to the arithmetic mean roughness of the back surface of the first layer that contacts the core or the second layer is 0.01 to 0.40." Specific examples and preferred examples of this configuration can be found on the relevant pages of the valve-forming ring of the second embodiment of the present invention, which will be described later.

[0130] In the first embodiment of the valve-forming ring of the present invention, it may also be as follows: "The first layer comprises an impregnation layer and a hydrogel layer composed of hydrogel, wherein the impregnation layer comprises a fabric or raw fabric impregnated with hydrogel, and the ratio of the stress of the hydrogel layer before water absorption treatment to the stress of the hydrogel layer after water absorption treatment is 0.05 to 0.80, and the water absorption treatment refers to placing the hydrogel layer in a solution at 30°C to 50°C for 30 minutes to 90 minutes." Specific examples and preferred embodiments of this embodiment can be found on the relevant pages of the third embodiment of the valve-forming ring of the present invention described later.

[0131] <Method for manufacturing a valve-forming ring according to a first aspect of the present invention>

[0132] The method for manufacturing the valve-forming ring of the present invention (hereinafter, sometimes abbreviated as the manufacturing method of the first aspect of the present invention) is a method for manufacturing a valve-forming ring comprising the above-described (1) annular core and (2) a first layer of fabric or fabric impregnated with hydrogel covering the surface of the core, including a step of irradiating the valve-forming ring with radiation (hereinafter, sometimes abbreviated as the irradiation step of the present invention).

[0133] The valve-forming ring, which is the object of manufacture in the manufacturing method of the present invention, is as described above.

[0134] More specifically, the manufacturing method of the present invention includes: a step of preparing the core of the first embodiment of the present invention (hereinafter, sometimes abbreviated as the core preparation step of the present invention), a step of preparing the first layer of the first embodiment of the present invention (hereinafter, sometimes abbreviated as the first layer preparation step of the present invention), and an irradiation step of the present invention.

[0135] The core preparation process of the present invention prepares the core of the first aspect of the present invention as described above. Specifically, for example, a commercially available stainless steel ring (e.g., MARUHO Clockwork Industry; stainless steel ring) is prepared and adjusted to the desired size as needed.

[0136] It should be noted that the core of the first aspect of the present invention is as described in the section on the valve shaping ring of the first aspect of the present invention above, and its specific examples, preferred examples, etc. are also the same.

[0137] The first layer preparation process of the present invention prepares the first layer of the first embodiment of the present invention as described above. Specifically, this is achieved by, for example, preparing a fabric or greige fabric impregnated with hydrogel, or more specifically, by winding the first layer of the first embodiment of the present invention around the core of the first embodiment of the present invention or the second layer of the first embodiment of the present invention and sewing it, or by directly covering it. As for the sewing method, any method commonly used in the field is acceptable; for example, hand sewing, sewing using a sewing machine, or other mechanical sewing methods can be cited. It should be noted that the first layer of the first embodiment of the present invention itself, as described in the section on the valve-forming ring of the first embodiment of the present invention above, is also as described in specific examples and preferred examples.

[0138] The irradiation process of the present invention is a process of irradiating a valve-forming ring containing the core of the first aspect of the present invention and the first layer of the first aspect of the present invention, obtained by the core preparation process and the first layer preparation process of the present invention, with radiation. By performing this process, the hydrogel in the valve-forming ring of the first aspect of the present invention is cross-linked by irradiation. The type of radiation, the irradiation method, etc., are as described in the above description of the valve-forming ring of the first aspect of the present invention, and specific examples and preferred examples are also as described.

[0139] The manufacturing method of the present invention may further include a step of adding a crosslinking agent to a valve ring comprising the core of the first embodiment of the present invention and the first layer of the first embodiment of the present invention, obtained by the core preparation step and the first layer preparation step of the present invention (hereinafter, sometimes abbreviated as the crosslinking agent addition step of the present invention). By performing this step, the hydrogel in the valve ring of the present invention is chemically crosslinked. The type of crosslinking agent, its crosslinking method, etc., are as described in the above-described section on the valve ring of the first embodiment of the present invention, as are specific examples and preferred examples.

[0140] In addition, the crosslinking agent addition process of the present invention is preferably performed after (1) the first layer preparation process of the present invention and before the irradiation process of the present invention or after (2) the irradiation process of the present invention.

[0141] The manufacturing method of the present invention may further include a step of preparing the second layer of the first aspect of the present invention (sometimes abbreviated as the second layer preparation step of the present invention). The second layer preparation step of the present invention prepares the second layer of the first aspect of the present invention as described above. In a specific example, it is a method for preparing a rubber-containing second layer existing between the core of the first aspect of the present invention and the first layer of the first aspect of the present invention. Specifically, examples include a method of covering the core of the first aspect of the present invention with the second layer of the first aspect of the present invention and sealing both ends with liquid silicone or the like, or a method of preparing a mold larger than the core of the first aspect of the present invention and inserting the core of the first aspect of the present invention and the second layer therein for integral molding. It should be noted that the second layer of the first aspect of the present invention itself, as described in the section on the valve molding ring of the first aspect of the present invention above, is also as described in specific examples and preferred examples.

[0142] The second layer preparation process of the present invention is preferably performed after the core preparation process of the present invention and before the first layer preparation process of the present invention.

[0143]

[0144] The valve repair kit of the first aspect of the present invention (hereinafter, sometimes abbreviated as the kit of the first aspect of the present invention) includes the valve repair ring of the first aspect of the present invention, and a ring holder and / or a ring measuring device. The valve repair ring of the first aspect of the present invention is as described above. The ring holder included in the kit of the first aspect of the present invention refers to a device for receiving the valve repair ring of the first aspect of the present invention. By using the ring holder, a physician or other medical practitioner can deliver the valve repair ring of the first aspect of the present invention to the intended position on the patient. Furthermore, the ring measuring device included in the kit of the first aspect of the present invention refers to a surgical instrument used manually during valve repair surgery for measuring the opening of the implanted valve repair ring.

[0145] The kit of the first aspect of the present invention may include an instruction manual as needed. The aforementioned instruction manual, which substantially describes the principle, features, and operating procedures of the valve-forming ring of the first aspect of the present invention through text, drawings, etc., may take the form of an instruction manual, drug instructions, brochures, promotional materials, etc.

[0146] The kit of the first aspect of the present invention is used in valvuloplasty for mitral valve diseases such as mitral regurgitation, mitral stenosis, or tricuspid valve diseases such as tricuspid stenosis, tricuspid regurgitation. By using the kit of the first aspect of the present invention, valvuloplasty can be performed simply, quickly, and accurately.

[0147] <Second embodiment of the valve-forming ring of the present invention>

[0148] The second aspect of the valve-forming ring of the present invention is characterized by comprising (1) an annular core and (2) a first layer comprising a fabric or raw fabric impregnated with hydrogel covering the surface of the core. Hereinafter, the second aspect of the valve-forming ring of the present invention will be described in detail.

[0149] [Core portion of the second embodiment of the present invention]

[0150] For specific examples, preferred examples, etc. of the core of the second aspect of the present invention, please refer to the relevant pages of the first aspect of the present invention described above.

[0151] [First layer of the second aspect of the present invention]

[0152] For specific examples, preferred examples, etc. of the first layer of the second aspect of the present invention, please refer to the relevant pages of the first layer of the present invention described above.

[0153] [Second layer of the second aspect of the present invention]

[0154] For specific examples, preferred examples, etc. of the second layer of the second aspect of the present invention, please refer to the relevant pages of the second layer of the first aspect of the present invention described above.

[0155] [Arithmetic mean roughness of the second aspect of the present invention]

[0156] The valve-forming ring of the second embodiment of the present invention has the above-described structure, and the ratio of the arithmetic mean roughness of the surface of the first layer of the second embodiment of the present invention, which is not in contact with the core or the second layer of the second embodiment of the present invention, to the arithmetic mean roughness of the back surface of the first layer of the second embodiment of the present invention, which is in contact with the core or the second layer of the second embodiment of the present invention, is, for example, 0.01 to 0.40, preferably 0.02 to 0.25, more preferably 0.03 to 0.2, and particularly preferably 0.04 to 0.15.

[0157] The arithmetic mean roughness described above represents the average distance from the baseline, with the average value of the surface's unevenness as the baseline. Therefore, the smaller the arithmetic mean roughness value, the fewer the unevennesses, and the smoother the surface can be described as.

[0158] As shown in the embodiments described later, the second aspect of the valve repair ring of the present invention surprisingly exhibits improved flexibility in the out-of-plane direction by setting the specific arithmetic mean roughness ratio described above. Therefore, the second aspect of the valve repair ring of the present invention preferably possesses the specific arithmetic mean roughness ratio described above.

[0159] It should be noted that the aforementioned flexibility in the outward direction is as follows: Figure 3 The figure shows the flexibility (expansion) of the valve repair ring along the Z-axis. Figure 3This diagram illustrates the flexibility of the valve-forming ring 1. Flexibility in the outward direction refers to flexibility (expansion) in the direction of arrow 5. Conversely, the opposite of "flexibility in the outward direction," namely flexibility in the inward direction, refers to flexibility (expansion) in the direction of arrow 6.

[0160] As a method for measuring the arithmetic mean roughness, any method commonly used in the field can be employed. For example, the valve repair ring of the second aspect of the present invention can be fixed on a platform parallel to the ground, and the roughness can be measured using a measuring instrument (e.g., a one-step 3D shape measuring instrument (KEYENCE, VR-6000)) under the following conditions. It should be noted that the following conditions are illustrative and not limiting. Furthermore, the area for measuring the arithmetic mean roughness can be the entire valve repair ring or a portion (e.g., an area after removing any arbitrarily 4 mm; for example, the two ends or the center portion when the annular valve repair ring is stretched into a straight line). Detailed measurement methods can also be found in the embodiments described later.

[0161] • Surface roughness specification: JIS B 0601:1994,2001

[0162] • Cutoff value: 0.8mm

[0163] • Reference value: 4mm

[0164] Furthermore, the following formula is used as a method for calculating the ratio of the above-mentioned arithmetic mean roughness.

[0165] <Formula 1>

[0166] The arithmetic mean roughness ratio = the arithmetic mean roughness of the surface of the first layer of the second embodiment of the present invention / the arithmetic mean roughness of the back surface of the first layer of the second embodiment of the present invention

[0167] The components, materials, characteristics, etc. of the valve repair ring of the second aspect of the present invention may be appropriately referred to the matters described in the valve repair ring of the first aspect of the present invention.

[0168] <Method for manufacturing a valve-forming ring according to a second aspect of the present invention>

[0169] The second aspect of the method for manufacturing a valve-forming ring of the present invention (hereinafter, sometimes abbreviated as the second aspect of the manufacturing method of the present invention) is a method for manufacturing a valve-forming ring comprising (1) the above-mentioned annular core and (2) a first layer of fabric or fabric impregnated with hydrogel covering the surface of the above-mentioned core, comprising: step 1 (hereinafter, sometimes abbreviated as step 1 of the second aspect of the present invention) of obtaining a composite of annular core and fabric or fabric by providing fabric or fabric on the outside of the annular core; step 2 (hereinafter, sometimes abbreviated as step 2 of the second aspect of the present invention) of obtaining an impregnated composite impregnated with hydrogel by contacting the above-mentioned composite with hydrogel; and step 3 (hereinafter, sometimes abbreviated as step 3 of the second aspect of the present invention) of contacting the above-mentioned impregnated composite with a crosslinking agent.

[0170] It should be noted that the valve repair ring, which is the object of manufacture in the manufacturing method of the second aspect of the present invention, is of course as described above. Therefore, the matters described in the section on the valve repair ring of the second aspect of the present invention (including, if necessary, the valve repair ring of the first aspect of the present invention) can be appropriately referred to.

[0171] [Step 1 of the second aspect of the present invention]

[0172] Step 1 of the second aspect of the present invention is a process of obtaining a composite of an annular core and fabric or greige fabric by placing fabric or greige fabric on the outside of the annular core.

[0173] Step 1 of the second aspect of the present invention is first performed by preparing the core of the second aspect of the present invention as described above. Specifically, for example, this is performed by preparing a commercially available stainless steel ring (e.g., MARUHO Clockwork Industry; stainless steel ring), and adjusting it to the desired size as needed.

[0174] It should be noted that the core of the second aspect of the present invention is as described in the relevant pages of the second aspect of the valve shaping ring of the present invention, as well as its specific examples, preferred examples, etc.

[0175] Following the above description, in step 1 of the second aspect of the present invention, a fabric or greige fabric is placed on the outer side (surface) of the core portion of the second aspect of the present invention. Specifically, this is performed by wrapping the fabric or greige fabric around the core portion of the second aspect of the present invention and then sewing or directly covering it. As for the sewing method, any method commonly used in the field is acceptable, for example, hand sewing, sewing using a sewing machine, or other mechanical sewing methods.

[0176] It should be noted that in the valve shaping ring of the second aspect of the present invention, when the second layer of the second aspect of the present invention is provided, the above-described step 1 is performed by providing the second layer of the second aspect of the present invention on the outer side (surface) of the core of the second aspect of the present invention, and then providing fabric or nylon on its outer side (surface). Specifically, methods in this case can include, for example, covering the core of the second aspect of the present invention with the second layer of the second aspect of the present invention and sealing both ends with liquid silicone or the like, or preparing a mold larger than the core of the second aspect of the present invention and inserting the core of the second aspect of the present invention and the second layer therein for integral molding.

[0177] It should be noted that the second layer of the second aspect of the present invention is itself as described in the relevant pages of the second aspect of the present invention valve annuloplasty ring (which may include the first aspect of the present invention valve annuloplasty ring if necessary), and its specific examples, preferred examples, etc. are also the same.

[0178] The composite of the annular core and the fabric or greige fabric can be obtained through step 1 of the second aspect of the present invention described above.

[0179] [Step 2 of the second aspect of the present invention]

[0180] Step 2 of the second aspect of the present invention is a process of obtaining a coated composite impregnated with hydrogel by contacting the composite obtained by step 1 of the second aspect of the present invention with hydrogel.

[0181] As a method for contacting the composite with the hydrogel, it can be implemented by methods commonly used in the field, specifically, for example, by methods described in the relevant pages of the second aspect of the present invention (methods such as spraying or coating hydrogel).

[0182] In step 2 of the second aspect of the present invention, in addition to the method described above, a molding method may also be used instead of the method described above. Specifically, the molding method involves fixing, for example, a composite onto the central axis of a container containing hydrogel. By using the above method, the hydrogel can be uniformly impregnated in the composite. Furthermore, the shape of the container can be, for example, a cylindrical shape, a triangular prism, a square prism, a pentagonal prism, or other prismatic shapes. In the molding method, the time for fixing the hydrogel is from a few seconds to 24 hours, the temperature during fixing is from 0°C to room temperature, and the drying time can be set as needed after fixing.

[0183] It should be noted that the hydrogel in step 2 of the second aspect of the present invention is itself as described in the relevant pages of the second aspect of the present invention valve-forming ring (which may include the first aspect of the present invention valve-forming ring if necessary), and its specific examples, preferred examples, etc. are also the same.

[0184] An impregnated composite containing hydrogel can be obtained through step 2 of the second aspect of the present invention as described above.

[0185] [Step 3 of the second aspect of the present invention]

[0186] Step 3 of the second aspect of the present invention is a step of contacting the impregnated composite obtained by step 2 of the second aspect of the present invention with a crosslinking agent. By performing step 3 of the second aspect of the present invention, the hydrogel itself in the valve-forming ring of the second aspect of the present invention is chemically crosslinked. The type of crosslinking agent, its crosslinking method, etc., are as described on the relevant pages of the valve-forming ring of the second aspect of the present invention (which may include the valve-forming ring of the first aspect of the present invention if necessary), and specific examples, preferred examples, etc., are also as described.

[0187] A valve-forming ring comprising (1) an annular core and (2) a first layer of fabric or fabric impregnated with hydrogel, which covers the surface of the core, can be manufactured by performing the steps 1 to 3 of the second aspect of the present invention described above.

[0188]

[0189] For specific examples and preferred examples of the valve repair kit of the second aspect of the present invention, please refer to the relevant pages of the valve repair kit of the first aspect of the present invention described above.

[0190] <The third-party valve shaping ring of the present invention>

[0191] The third-order valve-forming ring of the present invention is characterized by comprising: (1) an annular core, and a first layer comprising (2) an impregnation layer of fabric or raw fabric impregnated with hydrogel and a hydrogel layer, the surface of the core being covered circumferentially. Hereinafter, the details of the third-order valve-forming ring of the present invention will be described.

[0192] [The third-party core of the present invention]

[0193] For specific examples and preferred examples of the third-party core of the present invention, please refer to the relevant pages of the first embodiment of the present invention described above.

[0194] [First layer of the third aspect of the present invention]

[0195] The first layer of the third embodiment of the present invention covers the surface of the core of the third embodiment of the present invention circumferentially, comprising: an impregnation layer containing a fabric or raw fabric impregnated with hydrogel and a hydrogel layer. In the valve-forming ring of the third embodiment of the present invention, since the first layer of the third embodiment of the present invention, constructed with a specific structure, covers the surface of the core of the third embodiment of the present invention circumferentially, stress concentration can be suppressed as shown in the embodiments described later, thereby overcoming the stability problem caused by fatigue failure.

[0196] It should be noted that the circumference referred to here refers to the annular shape of the core of the third type of the present invention, and the meaning of "circumference" is the same as "the ring (shape) covering the core".

[0197] As the first layer of the third aspect of the present invention, the greige fabric or cloth is preferably a biocompatible greige fabric or cloth. Specifically, examples include biocompatible knitted fabrics and woven fabrics. As knitted fabrics, various warp and weft knitting structures can be used. Particularly preferred knitted fabrics include double-layer Raschel knitted fabrics, plain knitted fabrics, rubber knitted fabrics, Tricot fabrics, and Raschel fabrics. For example, the density of the warp-knitted fabric (in the undigested state of the bioabsorbable material) is preferably 20 rows / inch to 200 rows / inch and 20 rows / inch to 55 rows / inch. From the viewpoints of ease of sewing the greige fabric to the biological tissue, water resistance, needle hole leakage, and anisotropy of the warp-knitted fabric, it is more preferably 70 rows / inch to 110 rows / inch and 30 rows / inch to 45 rows / inch, and even more preferably 80 rows / inch to 100 rows / inch and 32 rows / inch to 42 rows / inch. As a fabric, plain weave, twill weave, and satin weave can be used.

[0198] In the third embodiment of the present invention, the fabric or greige fabric in the first layer is preferably composed of yarn made of bio-absorbent materials and / or non-bio-absorbent materials.

[0199] As for the wire made of the bio-absorbable material, there are no particular limitations as long as it is biocompatible and decomposes and is absorbed or disappears in the body over time. Specifically, for example, reference can be made to the relevant pages of the first layer of the first embodiment of the present invention.

[0200] As for the non-biological absorbent material, there are no particular limitations as long as it is biocompatible and decomposes or disappears within the body over time. Specifically, for example, reference can be made to the relevant pages of the first layer of the first embodiment of the present invention.

[0201] The first layer of the third aspect of the present invention includes an impregnation layer comprising a fabric or lining impregnated with hydrogel, which means that the fabric or lining is impregnated with hydrogel. Here, "impregnation" refers to, for example, the form in which the hydrogel permeates into the fabric or lining, or it can simply be the form in which the hydrogel covers (coats) the fabric or lining.

[0202] Specifically, for example, reference can be made to the relevant page of the first layer of the first embodiment of the present invention as the hydrogel.

[0203] The first layer of the third embodiment of the present invention comprises a hydrogel layer composed of hydrogel.

[0204] The hydrogel in the first layer of the third embodiment of the present invention, as described in the impregnation layer of the first layer of the third embodiment of the present invention, is a layer composed of hydrogel not impregnated in the fabric or greige fabric when the fabric or greige fabric comes into contact with the hydrogel. It can also be a layer composed solely of hydrogel, or substantially composed solely of hydrogel. The hydrogel in the above-described hydrogel layer, as described in the impregnation layer, can be referenced to specific examples, preferred examples, etc.

[0205] As a third aspect of the present invention, the composition and positional relationship of the impregnating layer and the hydrogel layer in the first layer can be exemplified by the following modes: (Mode 1) covering the surface of the core of the third aspect of the present invention with an impregnating layer and then covering its surface with a hydrogel layer; (Mode 2) covering the surface of the core of the third aspect of the present invention with a hydrogel layer and then covering its surface with an impregnating layer; (Mode 3) when the impregnating layer is a fabric or lining and the hydrogel is only in a covering relationship, covering the surface of the core of the third aspect of the present invention with a hydrogel layer, then covering its surface with a fabric or lining, and then covering its surface with a hydrogel; (Mode 4) when the impregnating layer is a fabric or lining and the hydrogel is only in a covering relationship, covering the surface of the core of the third aspect of the present invention with a fabric or lining, and then covering its surface with a hydrogel (including a hydrogel layer), etc.

[0206] The thickness of the first layer, as a third aspect of the present invention, can be appropriately set according to the patient applying the third-party valve annuloplasty ring of the present invention, for example, 100 micrometers to 2000 micrometers, preferably 130 micrometers to 1000 micrometers, more preferably 150 micrometers to 800 micrometers, further preferably 170 micrometers to 600 micrometers, and most preferably 200 to 450 micrometers.

[0207] [Second layer of the third aspect of the present invention]

[0208] In addition to the core and first layer of the third-party valve-forming ring described above, the third-party valve-forming ring of the present invention may also include a second layer containing rubber (hereinafter sometimes abbreviated as the second layer of the third embodiment of the present invention). The second layer of the third embodiment of the present invention, containing the rubber described later, is positioned between the core of the third-party embodiment and the first layer of the third embodiment of the present invention. Specific examples and preferred examples of the second layer of the third embodiment of the present invention can be found on the relevant pages concerning the second layer of the first embodiment of the present invention.

[0209] [Stress of the hydrogel in the third aspect of the present invention]

[0210] The third-party valve-forming ring of the present invention has the above-described structure, and the ratio of the stress of the hydrogel in the hydrogel layer before water absorption treatment to the stress after water absorption treatment is, for example, 0.05 to 0.80, preferably 0.07 to 0.60, more preferably 0.07 to 0.50, and particularly preferably 0.07 to 0.46. Alternatively, the ratio may be 0.07 (±0.02) or 0.4 (±0.02).

[0211] The aforementioned water absorption treatment refers to placing the hydrogel layer in a solution at 30°C to 50°C for 30 to 90 minutes. Preferably, the temperature is 37°C, the solution is water, and the placement time is 60 minutes. Specifically, examples of the water include ultrapure water, pure water, deionized water, and purified water, with ultrapure water being the most preferred.

[0212] The stress mentioned above refers to the stress per unit area (mm²) 2 The stress generated (N / mm) 2 This stress, sometimes referred to as stress, can be measured, for example, by determining the thickness (film thickness) of the hydrogel sample using a specified testing machine (e.g., Shimadzu EZ-SX). Specifically, it is performed by clamping the sample from above and below at a position 8.5 mm from one end using a tensile clamp (e.g., Shimadzu 500N screw-type flat clamp), displacing the sample until it breaks, and recording the stress at fracture (at a speed of, for example, 200 mm / min). Furthermore, detailed measurement methods can be found in the embodiments described later.

[0213] The third-party valve-forming ring of the present invention, as shown in the embodiments described later, surprisingly exhibits the ability to suppress stress concentration in each segment by using the specific ratio described above. As a result, stability problems caused by fatigue failure can be overcome. Regarding this parameter (ratio), the inventors discovered that the hydrogel tends to break down due to water absorption when the degree of crosslinking is low, and based on this insight, this parameter was set for the first time. Thus, the inventors first elucidated the correlation between this parameter and the suppression of stress concentration.

[0214] Therefore, the third-party valve-forming ring of the present invention preferably has the specific ratio described above.

[0215] Alternatively, the above ratio can be calculated using the following formula.

[0216] <Formula 2>

[0217] Ratio = Stress value after water absorption treatment / Stress value before water absorption treatment

[0218] The components, materials, characteristics, etc. of the third-party valve repair ring of the present invention may be appropriately referred to the matters described in the first-party valve repair ring of the present invention.

[0219] <The third-party method for manufacturing the valve-forming ring of the present invention>

[0220] The third-party method for manufacturing a valve-forming ring of the present invention (hereinafter, sometimes abbreviated as the third-party method of the present invention) is a method for manufacturing a valve-forming ring comprising (1) the above-mentioned annular core and (2) a first layer covering the surface of the above-mentioned core on the circumference, wherein the first layer comprises an impregnation layer of fabric or prefabricated fabric impregnated with hydrogel and a hydrogel layer composed of hydrogel, wherein the manufacturing method comprises: step 1 (hereinafter, sometimes abbreviated as step 1 of the third-party method of the present invention) of obtaining a composite of annular core and fabric or prefabricated fabric by providing fabric or prefabricated fabric on the outside of the annular core; and step 2 (hereinafter, sometimes abbreviated as step 2 of the third-party method of the present invention) of obtaining a first layer comprising an impregnation layer of fabric or prefabricated fabric impregnated with hydrogel and a hydrogel layer composed of hydrogel by contacting the above-mentioned composite with hydrogel.

[0221] It should be noted that the valve repair ring, which is the object of manufacture in the manufacturing method of the present invention, is of course as described above. Therefore, the matters described in the relevant pages of the third-party valve repair ring of the present invention can be appropriately referred to.

[0222] [Third-party process 1 of the present invention]

[0223] The third-party process 1 of the present invention is a process of obtaining a composite of an annular core and fabric or greige fabric by placing fabric or greige fabric on the outside of the annular core.

[0224] The third-party process 1 of the present invention is first performed by preparing the core of the present invention as described above. Specifically, for example, it is performed by preparing a commercially available stainless steel ring (e.g., MARUHO Clockwork Industry; stainless steel ring), and adjusting it to the desired size as needed.

[0225] It should be noted that the third-party core of the present invention is as described in the relevant pages of the third-party valve shaping ring of the present invention, and its specific examples, preferred examples, etc. are also the same.

[0226] Following the above description, in the third-party process 1 of the present invention, a fabric or greige fabric is provided on the outer side (surface) of the core of the third-party process of the present invention. Specifically, this is performed by wrapping the fabric or greige fabric around the core of the present invention and sewing it or by directly covering it. As for the sewing method, any method commonly used in the field is acceptable, for example, hand sewing, sewing using a sewing machine or other mechanical sewing methods can be cited.

[0227] It should be noted that when the second layer of the third aspect of the present invention is provided in the valve shaping ring of the third aspect of the present invention, the above-described step 1 is performed by providing the second layer of the third aspect of the present invention on the outer side (surface) of the core of the third aspect of the present invention, and then providing fabric or raw fabric on its outer side (surface). Specifically, methods in this case can include, for example, covering the core of the third aspect of the present invention with the second layer of the third aspect of the present invention and sealing both ends with liquid silicone, or preparing a mold larger than the core of the third aspect of the present invention and inserting the core of the third aspect of the present invention and the second layer therein for integral molding.

[0228] It should be noted that the second layer of the third aspect of the present invention is itself as described in the relevant pages of the third aspect of the valve shaping ring of the present invention, and its specific examples, preferred examples, etc. are also the same.

[0229] A composite of annular core and fabric or greige fabric can be obtained through the third-party process 1 of the present invention described above.

[0230] [Third-party process 2 of the present invention]

[0231] The third-party process 2 of the present invention is a process of obtaining a first layer comprising a composite obtained by the third-party process 1 of the present invention, an impregnation layer comprising a fabric or greige fabric impregnated with hydrogel, and a hydrogel layer composed of hydrogel.

[0232] As a method for contacting the composite with the hydrogel, it can be implemented using methods commonly practiced in the field, specifically, for example, the method described in the section on the third-party valve-forming ring of the present invention (methods such as spraying or coating hydrogel).

[0233] In step 2 of the third aspect of the present invention, in addition to the method described above, a molding method may also be used instead of the method described above. Specifically, as a method of using the molding method, for example, there is a method of fixing the composite to the central axis of a container containing hydrogel. By using the above method, the hydrogel can be uniformly impregnated in the composite. Furthermore, as for the shape of the container, for example, prisms such as cylindrical, triangular prism, square prism, and pentagonal prism can be used. In the method of using the molding method, the time for fixing the hydrogel is from a few seconds to 24 hours, the temperature during fixing is from 0°C to room temperature, and the drying time after fixing can be set as needed.

[0234] It should be noted that the hydrogel in step 2 of the third-party method of the present invention is itself as described on the relevant pages of the third-party method valve forming ring of the present invention, and its specific examples, preferred examples, etc. are also the same.

[0235] A first layer comprising an impregnation layer containing a fabric or greige fabric impregnated with hydrogel and a hydrogel layer composed of hydrogel can be obtained through the third-party process 2 of the present invention described above.

[0236] In the third-party manufacturing method of the present invention, following steps 1 and 2 of the third-party method of the present invention described above, a step of adding a crosslinking agent (hereinafter sometimes abbreviated as step 3 of the third-party method of the present invention) can be performed. By performing step 3 of the third-party method of the present invention, the hydrogel itself in the valve-forming ring of the third-party method of the present invention is chemically crosslinked. The type of crosslinking agent, its crosslinking method, etc., are as described in the section on the valve-forming ring of the third-party method of the present invention described above, and specific examples, preferred examples, etc., are also the same.

[0237] <The third-party valve repair kit of the present invention>

[0238] The third-party valve repair kit of the present invention (hereinafter, sometimes abbreviated as the third-party kit of the present invention) includes the third-party valve repair ring of the present invention, as well as a ring holder and / or a ring measuring device. The third-party valve repair ring of the present invention can be found on the relevant pages of the first-ideal valve repair kit of the present invention described above.

[0239] Example

[0240] The present invention will now be described in more detail with reference to embodiments, but the scope of the invention is not limited thereto.

[0241] The following describes manufacturing examples, embodiments, and comparative examples related to the valve reshaping ring of the first aspect of the present invention.

[0242] <Manufacturing Example 1; Manufacturing of the Valve Molding Ring of the Present Invention>

[0243] A stainless steel ring (manufactured by MARUHO Clockwork Industry, 700 micrometers in diameter) was used as the core material, and its outer periphery was covered with a silicone tube (manufactured by SILICONE TECHNO). Liquid silicone (manufactured by Momentive Materials Japan, TSE382-C) was filled into both ends and sealed by standing overnight at 50°C. Then, polyethylene terephthalate yarn (33T15) was used on the outside, and a fabric (manufactured by Fukui Warp Knitting Industry) with a density of 38-39 rows / inch and 90 rows / inch was wound around it and sewn together (hereafter referred to as the sample in this manufacturing example 1).

[0244] Then, the sample was immersed in Milli-Q and degassed at 50°C and below 15 hPa for at least 30 minutes. Next, the sample was slowly immersed in a 9.5% w / w gelatin solution (made by Nitta Gelatin; beMatrix Gelatin LS-H) at 50°C and allowed to stand at 50°C. After 15 minutes, the sample was slowly removed and placed on a thread (made by Toray, 0.1) with the seam side facing up and allowed to stand. After 5 minutes, the sample was slowly immersed in the gelatin solution again, and then immediately and slowly removed and placed on the thread with the seam side facing down and allowed to stand. After 5 minutes, the sample was slowly immersed in the gelatin solution again, and then immediately and slowly removed and placed on the thread with the seam side facing up and allowed to stand. After 5 minutes, the sample was slowly immersed in the gelatin solution again, and then immediately and slowly removed and placed on the thread with the seam side facing down and allowed to stand. The sample was dried at room temperature for 30 minutes, then immersed in 15 mL of 0.2% glutaraldehyde solution (Tokyo Chemical Industry Co., Ltd., 50% glutaraldehyde solution) and reacted at room temperature for 3 hours. After the reaction, it was immersed in 15 mL of 60% glycerol aqueous solution (Kenei Pharmaceutical Co., Ltd., pharmacopoeia-grade glycerol) and allowed to stand at room temperature for 30 minutes. The solution was then replaced with fresh glycerol aqueous solution. This process was repeated twice. After the third glycerol wash, the sample was removed and dried overnight at room temperature to obtain a valve-forming ring. The obtained valve-forming ring was then placed in an aluminum bag containing silica gel desiccant (Toyota Chemical Industry Co., Ltd., PC(silo) 5G) and a deoxidizer (Oe Chemical Industry Co., Ltd., Tamotsu VX100), and irradiated with a 30 kGy electron beam in the presence of dry ice (electron beam irradiation was performed by SHI-ATEX). Thus, the valve-forming ring of the present invention was obtained.

[0245] It should be noted that the other experimental conditions in the electron beam irradiation described above are as follows.

[0246] Irradiation device: Electron beam irradiation device (e.g., RDI; high-frequency, high-voltage electron accelerator).

[0247] Radiation dosing apparatus: CTA radiation dosimeter apparatus (e.g., Shimadzu UV1800 spectrophotometer).

[0248] Radiation meter: CTA radiation meter (e.g., Fujifilm FTR-125).

[0249] Accelerating voltage: 4.8 megavolts

[0250] Current: 20 mA

[0251] Vehicle speed (outer perimeter): 18.0 m / min

[0252] Irradiation direction: single-sided

[0253] Number of irradiations: 2

[0254] Supporting material: laminated corrugated paper

[0255] Other: Pre-irradiation absorbance measurement of the radiometer is performed before electron beam irradiation. Additionally, after electron beam irradiation, the radiometer is removed and the post-irradiation absorbance is measured. The radiation dose is calculated based on the difference between the pre-irradiation and post-irradiation absorbance.

[0256] <Manufacturing Example 2; Manufacturing of the Valve Molding Ring of the Present Invention>

[0257] The glutaraldehyde concentration was changed to 0.05%, and the valve-forming ring of the present invention was manufactured in the same manner as in Manufacturing Example 1.

[0258] <Manufacturing Example 3; Manufacturing of the Valve Molding Ring of the Present Invention>

[0259] The glutaraldehyde concentration was changed to 1.5%, and the valve-forming ring of the present invention was manufactured in the same manner as in Manufacturing Example 1.

[0260] <Manufacturing Example 4; Manufacturing of Valve Reshaping Ring>

[0261] A valve forming ring is manufactured by winding a fabric made of polyethylene terephthalate onto the core material described in Manufacturing Example 1.

[0262] <Manufacturing Example 5; Manufacturing of Valve Reshaping Ring>

[0263] The same valve-forming ring as described in Manufacturing Example 1 was manufactured (but not irradiated with an electron beam).

[0264] <Examples 1-3, Comparative Examples 1 and 2; Implementation of the Hemolytic Test>

[0265] [Sample preparation for hemolysis test]

[0266] The valve-forming ring of the present invention, manufactured in Examples 1-3 and 5, was cut into 7mm × 10mm sheets from its suture side using a scalpel. The cross-sections at both ends were observed using a microscope (KEYENCE, VHX8000), and the thickness of the gelatin gel, including the fabric at the top, was measured. The average value of these measurements was taken as the film thickness.

[0267] Next, the samples with the film thickness measured above were placed on a 1cm×1cm rubber sheet (manufactured by ASONE, silicone rubber sheet 1t 500 square) with the silicone tube side facing down, and sewn together with ETHIBOND5-0 (registered trademark) (manufactured by Johnson & Johnson) to prepare samples for the hemolytic reaction test. Then, an appropriate amount of silicone adhesive (Momentive Advanced Materials Japan, TSE392W) was applied to the back of the sample, and it was fixed to the bottom of a polypropylene (PP) container (manufactured by Maruemu, 14mL No.4) with the adhesive.

[0268] It should be noted that for the valve-forming ring of Manufacturing Example 4, film thickness measurement was not performed, and the hemolysis test sample was prepared using the same steps as in Manufacturing Examples 1-3 and 5. Additionally, a hemolysis test sample composed solely of the aforementioned silicone rubber was also prepared using the above method.

[0269] [Preparation of tubes for hemolysis test]

[0270] Cut a 45cm section from the pump tubing (ASONE, 3.2×6.4mm high-strength roller-rolled silicone tubing). Next, cut a 2mL pipette (SUMILON, aligning with the 1.1mL mark) and insert the cut 2mL pipette into one end of the 45cm tubing. To prevent blood from being blocked by pipette fragments, use a metering pump (EYELA, NRP-3000) to draw Milli-Q water from the nozzle and drain it from the silicone tubing side. Additionally, to check for nozzle malfunctions, drain Milli-Q water from the silicone tubing side and drain it from the nozzle side. Discard any malfunctioning nozzle tubing, drain the water from the good tubing, and allow the tubing to dry completely.

[0271] [Confirmation of hemolysis]

[0272] Hemolysis confirmation was performed on purchased blood (rabbit whole blood with added sodium citrate, manufactured by SLC, Japan). 0.2 mL of blood was added to 10 mL of physiological saline (500 mL plastic bottle, manufactured by Otsuka Pharmaceutical Co., Ltd.) in a 15 mL Corning polypropylene centrifuge tube. Centrifugation was performed at 750 × g for 5 minutes using a high-speed centrifuge (HITACHI CF16RN). For each sample, 200 μL of the supernatant was added to three wells of a 96-well plate (VIOLAMO). The optical density (OD) was measured using a microplate reader (Molecular Devices Japan SpectraMax190) at a wavelength of 576 nm. All samples with an OD below 0.014 were used for the experiment.

[0273] [Flow Confirmation]

[0274] The average flow rate was determined using a metered infusion pump and tubing based on the volume of Milli-Q water discharged every 30 seconds and the diameter of the pipette. The rotation speed was set to an average flow rate of 7 m / s.

[0275] [Adjustment of negative and positive control blood]

[0276] Add 600 μL of physiological saline and 600 μL of blood to a 1.5 mL tube (Hitec, 1.5 mL protein-low adsorption microtube) and incubate at 37°C for 70 minutes (as a negative control). Add 600 μL of distilled water (Otsuka Pharmaceutical Co., Ltd., 500 mL plastic bottle) and 600 μL of blood to a 1.5 mL tube and incubate at 37°C for 70 minutes (as a positive control). Centrifuge the 1.5 mL tubes using a microcentrifuge (KUBOTA, Model 3740) at 800×g for 5 minutes. For the negative control, add 200 μL of supernatant to 3 wells of a 96-well plate. For the positive control, dilute 10-fold (N=3) by adding 180 μL of distilled water and 20 μL of supernatant to the 96-well plate. Measure the OD (wavelength 576 nm) using a microplate reader.

[0277] [Implementation of the hemolytic test]

[0278] The quantitative infusion pump was placed in a large incubator (Thermo Model 3950) set to 38.5°C. 5 mL of physiological saline was added to a 15 mL centrifuge tube, followed by 5 mL of blood to prepare a 2-fold dilution. The blood was then heated in a 37°C water bath for 10 minutes. The PP container was vertically mounted on the clamp, with the silicone tube side of the nozzle in contact with the bottom of the PP container. The sample's long axis was positioned as the depth direction. The nozzle was fixed to the clamp at a height of 3 mm vertically from the sample surface, ensuring the blood impacted the contact surface at a velocity within a range equal to 12 times the nozzle radius. A certain amount of heated blood was transferred from the centrifuge tube into the PP container at a low speed to prevent air ingress. The remaining blood from the centrifuge tube was transferred into the PP container using a power pipette (Drummond, Pipet-Aid XP). Blood was pumped into the sample at a flow rate of 7 m / s, pre-determined during flow confirmation, for 1 hour. After the experiment, all blood was collected and stored in 15 mL centrifuge tubes. The tubes were centrifuged at 750 × g for 5 minutes using a high-speed centrifuge. 200 μL of the supernatant from each sample was added to three wells of a 96-well plate, and the OD (wavelength 576 nm) was measured using a microplate reader. If the absorbance of the supernatant was high, it was appropriately diluted and measured. The hemolysis rate was then calculated based on Equation 3 below.

[0279] <Formula 3>

[0280] Hemolysis rate = (Absorbance of the target sample - Absorbance of the negative control) / (Absorbance of the positive control - Absorbance of the negative control) - (Absorbance of the sample composed only of silicone rubber - Absorbance of the negative control) / (Absorbance of the positive control - Absorbance of the negative control)

[0281] It should be noted that after all samples were tested, the average flow rate was calculated based on the Milli-Q discharge rate every 30 seconds and the diameter of the pipette, confirming that the average flow rate did not change significantly compared to the beginning.

[0282] [Results of the hemolytic test]

[0283] As described above, the results of the hemolysis test of the samples used for the hemolysis test of the valve annuli from Manufacturing Examples 1 to 5 are shown in Table 1 below.

[0284] For convenience, the results related to the manufacture of the valve annuloplasty rings of Examples 1 to 3 are referred to as Examples 1 to 3, and the results related to the manufacture of the valve annuloplasty rings of Examples 4 and 5 are referred to as Comparative Examples 1 and 2, respectively.

[0285]

[0286] As shown in Table 1, when using the valve-forming rings of Manufacturing Examples 1-3, i.e., the valve-forming rings of the present invention, the hemolysis rates were 14% (Example 1), 15.6% (Example 2), and 23.6% (Example 3), respectively. On the other hand, when using the valve-forming rings of Manufacturing Examples 4 and 5, the hemolysis rates were 120.5% (Comparative Example 1) and 42.3% (Comparative Example 2), respectively. As a result, it can be seen that the valve-forming ring according to the present invention can significantly suppress the hemolysis rate. In particular, by comparing Example 1 with Comparative Example 2, it was surprisingly found that the hemolysis rate was significantly improved by irradiation with an electron beam. Furthermore, when comparing Examples 1 and 2 with Example 3, it was also found that the hemolysis rate was further improved by reducing the glutaraldehyde concentration (e.g., less than 1.5%).

[0287] Based on the above results, it can be seen that the valve-forming ring of the present invention is extremely superior from the viewpoint of hemolysis rate.

[0288] The following describes manufacturing examples, embodiments, and comparative examples related to the valve reshaping ring of the second aspect of the present invention.

[0289] <Manufacturing Example 6; Manufacturing of the Valve Molding Ring of the Present Invention>

[0290] Using 80mm of stainless steel wire (manufactured by HIKARI MOGOL, 0.7mm stainless steel wire) as the core material, a silicone tube (manufactured by SILICONE TECHNO) is coated around its outer periphery, and then a fabric (manufactured by Fukui Warp Knitting Industry) with a density of 38-39 rows / inch and 90 rows / inch is made of polyethylene terephthalate thread (manufactured by Teijin, 33T12) is wound around its outer side and sewn together (hereafter referred to as the sample in this manufacturing example 6).

[0291] Next, a 10mm silicone tube measuring 0.7×2.0mm (made by LABORAN) is installed at one end of the core material with the fabric in the center. Then, a 10mm silicone tube measuring 2.0×4.0mm (made by LABORAN) and a 10mm silicone tube measuring 4.0mm×6.0mm (made by LABORAN) are installed on top of it. Finally, a 80mm silicone tube measuring 6.0×8.0mm (made by LABORAN) is installed from above, thus preparing the mold.

[0292] In the mold, inject 1.2 mL to 1.4 mL of a 9.5% w / w gelatin solution (made by Nitta Gelatin, beMatrixGelatin LS-H) at 50°C along with the sample. Attach the silicone tube to the other end of the mold and cap it. After standing in a 4°C refrigerator for 30 to 60 minutes, remove the sample from the refrigerator and use a scalpel to make two incisions at 5 mm to 7 mm intervals on the side of the silicone tube. Tear open the incision area and remove the silicone tube.

[0293] The extracted sample was immersed in a 0.05% glutaraldehyde solution (Tokyo Kasei, 50% glutaraldehyde solution) and reacted at room temperature for 3 hours. After the reaction, it was immersed in a 60% glycerol aqueous solution (Kenei Pharmaceutical, pharmacopoeia-grade glycerol) and left to stand at room temperature for 30 minutes. Then, the solution was replaced with fresh glycerol aqueous solution. This operation was performed twice. After the third cleaning with glycerol aqueous solution, the sample was removed and dried overnight at room temperature, thereby obtaining the valve-forming ring of the present invention.

[0294] <Manufacturing Example 7; Manufacturing of the Valve Molding Ring of the Present Invention>

[0295] The glutaraldehyde concentration was changed to 0.5%, and the valve-forming ring of the present invention was manufactured in the same manner as in Manufacturing Example 6.

[0296] <Manufacturing Example 8; Manufacturing of the Valve Molding Ring of the Present Invention>

[0297] Using 80mm of stainless steel wire (manufactured by HIKARI MOGOL, 0.7mm stainless steel wire) as the core material, and covering its outer periphery with silicone tubing (manufactured by SILICONE TECHNO), a fabric (manufactured by Fukui Warp Knitting Industry) with a density of 38-39 rows / inch and 90 rows / inch, made of polyethylene terephthalate thread (manufactured by Teijin, 33T12), is wound around its outer side and sewn together (hereafter referred to as the sample in this manufacturing example 8).

[0298] Then, the sample was slowly immersed in a 9.5% w / w gelatin solution (made by Nitta Gelatin; beMatrixGelatin LS-H) at 50°C and left to stand for at least 15 minutes at 50°C. The sample was then slowly removed and left to stand at room temperature to allow the fabric portion to float. After 5 minutes, the sample was slowly immersed in the gelatin solution again, and then immediately and slowly removed and left to stand at room temperature for at least 30 minutes.

[0299] Next, a 10mm silicone tube measuring 0.7×2.0mm (made by LABORAN) is installed at one end of the core material with the fabric in the center. Then, a 10mm silicone tube measuring 2.0×4.0mm (made by LABORAN) and a 10mm silicone tube measuring 4.0mm×6.0mm (made by LABORAN) are installed on top of it. Finally, a 80mm silicone tube measuring 6.0×8.0mm (made by LABORAN) is installed from above, thus preparing the mold.

[0300] Inject 1.2 mL to 1.4 mL of a 9.5% w / w gelatin solution (made by Nitta Gelatin, beMatrixGelatin LS-H) at 50°C into the mold along with the sample. Attach the silicone tube to the other end of the mold and cap it. After standing in a 4°C refrigerator for 30 to 60 minutes, remove the sample from the refrigerator and use a scalpel to make two incisions at 5 mm to 7 mm intervals on the side of the silicone tube. Tear open the incision area and remove the silicone tube.

[0301] The extracted sample was immersed in a 0.2% glutaraldehyde solution (Tokyo Kasei, 50% glutaraldehyde solution) and reacted at room temperature for 3 hours. After the reaction, it was immersed in a 60% glycerol aqueous solution (Kenei Pharmaceutical, pharmacopoeia-grade glycerol) and allowed to stand at room temperature for 30 minutes. Then, the solution was replaced with fresh glycerol aqueous solution. This operation was repeated twice. After the third washing with glycerol aqueous solution, the sample was removed and dried overnight at room temperature, thereby obtaining the valve-forming ring of the present invention.

[0302] <Manufacturing Example 9; Manufacturing of Valve Reshaping Ring>

[0303] A valve forming ring is manufactured by winding a fabric made of polyethylene terephthalate onto the core material described in Manufacturing Example 6.

[0304] <Manufacturing Example 10; Manufacturing of Valve Reshaping Ring>

[0305] A valve-forming ring is manufactured by winding a fabric made of polyethylene terephthalate around the core material described in Manufacturing Example 6, and then winding a silicone tube around its outer periphery.

[0306] <Measurement of Arithmetic Mean Roughness Ratio>

[0307] Test pieces of 4 mm or more were cut from the valve-forming rings of the present invention manufactured in Examples 6-8 and 10. Both sides of the samples were colored using a color spray (Shinto Family, Color Spray Zero) and then dried. Next, the arithmetic mean roughness of the surface and back surfaces of any 4 mm range of the valve-forming ring of the present invention was measured using a one-step 3D shape measuring instrument (KEYENCE, VR-6000) (details described below). Specifically, the arithmetic mean roughness was measured at three locations: both ends and the center portion, when the annular valve-forming ring was stretched into a straight line.

[0308] Here, in manufacturing examples 6-8, the "surface" refers to the surface of the fabric impregnated with hydrogel (corresponding to the first layer of the second embodiment of the present invention) and is the surface that does not contact the silicone tube (corresponding to the second layer of the second embodiment of the present invention). Furthermore, the "back side" refers to the back side of the fabric impregnated with hydrogel (corresponding to the first layer of the second embodiment of the present invention) and is the surface that contacts the silicone tube (corresponding to the second layer of the second embodiment of the present invention).

[0309] On the other hand, in manufacturing example 10, the surface refers to the surface of the silicone tube and is the side that does not contact the fabric made of polyethylene terephthalate. Additionally, the back side refers to the back side of the silicone tube and is the side that contacts the fabric made of polyethylene terephthalate.

[0310] Next, the ratio of the arithmetic mean roughness of the surface to the back surface is calculated based on Equation 4 below.

[0311] <Formula 4>

[0312] Arithmetic mean roughness ratio = (Arithmetic mean roughness value of the surface of the first layer of the second embodiment of the present invention) / (Arithmetic mean roughness value of the back surface of the first layer of the second embodiment of the present invention)

[0313] <Measurement Conditions>

[0314] • Surface roughness specification: JIS B 0601:1994,2001

[0315] • Cutoff value: 0.8mm

[0316] • Reference value: 4mm

[0317] <Determination of softness in the outward direction>

[0318] The valve rings of the present invention manufactured in Examples 6-8 and Examples 9 and 10 were left in a low-temperature thermo-humidifier set at 37°C and 80%RH for more than 24 hours to allow them to swell. The improvement rate of softness was evaluated using a small benchtop testing machine (Shimadzu Corporation, EZ-SX).

[0319] Specifically, each valve annuloplasty ring was placed on a fixture (Akimoto Hikaru's mechanism) and positioned on a compression stage. A Φ1cm compression bar was used to press the central portion in the compression direction, and the load at a displacement of 1.07 mm was recorded (speed: 2.5 mm / min). The obtained load values ​​were then used to evaluate the improvement rate of flexibility in the outward direction for each valve annuloplasty ring. Here, in this measurement system, as described above, the force (load) required for the valve annuloplasty ring to move (displace) by 1.07 mm was measured. This is based on the correspondence between the outward movement of the annuloplasty ring and the 1.07 mm movement (displacement) of the annuloplasty ring (reference; J Anatomy, 2020; 237: 209-224). Therefore, through the above measurement, the load (force) at a displacement of 1.07 mm can be measured, and the lower the value, the better the flexibility in the outward direction can be deduced.

[0320] More specifically, the evaluation method described above uses the load value of the valve-forming ring of Manufacturing Example 9, which has the simplest configuration, as a benchmark. The load values ​​of the valve-forming rings of Manufacturing Examples 6-8 and 10 are divided by the value of the valve-forming ring of Manufacturing Example 9 to evaluate the improvement rate of softness in the outward direction. For example, when the load value of the valve-forming ring of Manufacturing Example 9 is 1.0 and the load value of the valve-forming ring of Manufacturing Example 6 is 0.7, setting the load value of the valve-forming ring of Manufacturing Example 9 (1.0) as 100%, the load value of the valve-forming ring of Manufacturing Example 6 (0.7) is 70%. Based on this calculation result, the improvement rate of softness in the outward direction of the valve-forming ring of Manufacturing Example 6 is evaluated as 30% (100% - 70%). Therefore, it can be said that the higher the value (%) indicating this improvement rate of softness, the better the softness in the outward direction.

[0321] <Determination of the solubility of gelatin>

[0322] The solubility of the gelatin in the valve-forming rings manufactured in Examples 6 to 9 was measured. Specifically, for each gelatin used in Examples 6 to 9, a gelatin film was prepared, and the film was placed in an aqueous solution at 37°C for 1 hour. Its condition was visually confirmed, and the solubility was measured accordingly.

[0323] <Summary of Evaluation Results>

[0324] The arithmetic mean roughness ratio, out-of-plane softness, and results related to the solubility of gelatin obtained using the valve molding rings of Examples 6-10 are shown in Table 2 below.

[0325] For convenience, the results related to the valve rings manufactured in Examples 6-8 are referred to as Examples 4-6, and the results related to the valve rings manufactured in Examples 9 and 10 are referred to as Comparative Examples 3 and 4, respectively.

[0326]

[0327] As shown in Table 2 above, the valve shaping rings of Examples 6 to 8 have a softness improvement rate (%) of 30% (Example 4), 11% (Example 5), and 19% (Example 6), and an arithmetic mean roughness ratio of 0.09 (Example 4), 0.04 (Example 5), and 0.14 (Example 6), respectively.

[0328] On the other hand, according to the valve shaping ring of Comparative Example 4, the value (%) indicating the improvement rate of softness in the outward direction is 5%, and the ratio of arithmetic mean roughness is 1.33.

[0329] Therefore, it can be seen that by supporting a valve-forming ring with a specific arithmetic mean roughness ratio (e.g., 0.04 to 0.14) as in Examples 4 to 6, the out-of-plane flexibility is improved. Furthermore, since it is not soluble in gelatin in addition to being flexible, it also possesses stability. Moreover, when comparing Examples 4 and 6 with Example 5, it can be seen that by setting the arithmetic mean roughness ratio to 0.09 (Example 4) to 0.14 (Example 6), the flexibility is further improved (30% compared to Example 4, 19% compared to Example 6, and 11% compared to Example 5). It can also be seen that, in particular, the flexibility is maximized (30%) by setting the arithmetic mean roughness ratio to 0.09 (Example 4).

[0330] Based on the above results, it is evident that the valve repair ring of the present invention is also extremely superior from the viewpoint of outward flexibility. In a valve repair ring, good outward flexibility allows it to conform to the natural movements during use, further reducing the risk of separation between biological tissue and the valve repair ring. Therefore, it can be said that the valve repair ring of the present invention, possessing this flexibility, has made a significant contribution to the field of technology.

[0331] It should be noted that for the valve annuloplasty rings related to Examples 4-6, it can be inferred that even if electron beam irradiation is performed as in Examples 1-3 above, the same results as described above will be obtained.

[0332] The following describes manufacturing examples, embodiments, and comparative examples related to the third-party valve-forming ring of the present invention.

[0333] <Manufacturing Example 11; Manufacturing of Gelatin Sheets>

[0334] A release film (Teijin-DuPont Purex) and a stainless steel frame (Akimoto Hikari Machinery) were placed in a polystyrene square box (ASONE, Type 5). A 9.5% w / w gelatin solution (Nitta Gelatin, beMatrix Gelatin LS-H) and the polystyrene square box were preheated to 65°C. 5 mL of gelatin was then evenly added dropwise into the stainless steel frame. If the gelatin was unevenly distributed, the box was covered and allowed to stand at 65°C until dissolved. The gelatin was then dried at room temperature for 30 minutes. The dried sample was then immersed in 0.05% glutaraldehyde (Tokyo Chemical) and reacted at room temperature for 3 hours. After the reaction, the sample was immersed in a 60% glycerol aqueous solution (Kenei Pharmaceutical, pharmacopoeia-grade glycerol) and allowed to stand at room temperature for 30 minutes. The solution was then replaced with a fresh glycerol aqueous solution. This process was repeated twice. After the third rinse with the glycerol aqueous solution, the sample was removed and vacuum dried to obtain gelatin sheets.

[0335] <Manufacturing Example 12; Manufacturing of Gelatin Sheets>

[0336] The glutaraldehyde concentration was changed to 0.2%, and the gelatin sheet was manufactured in the same manner as in Manufacturing Example 11.

[0337] <Manufacturing Example 13; Manufacturing of Gelatin Sheets>

[0338] The glutaraldehyde concentration was changed to 0.3%, and the gelatin sheet was manufactured in the same manner as in Manufacturing Example 11.

[0339] <Manufacturing Example 14; Manufacturing of Gelatin Sheets>

[0340] The glutaraldehyde concentration was changed to 0.5%, and the gelatin sheet was manufactured in the same manner as in Manufacturing Example 11.

[0341] <Stress Measurement>

[0342] Gelatin sheets manufactured in Examples 11-14 were cut using a dumbbell-shaped No. 8 die-cutting tool (for convenience, the cut gelatin sheets are sometimes referred to as test sheets). Next, the thickness of the test sheets before and after water absorption treatment was measured at three points: the upper, middle, and lower parts, using a film thickness gauge (Mitutoyo, VL-50). The average value of these measurements was taken as the film thickness of the sample. Then, the stress of each gelatin sheet before and after water absorption treatment was evaluated using a small benchtop testing machine (Shimadzu, EZ-SX).

[0343] Here, the above-mentioned water absorption treatment refers to placing the gelatin sheet in ultrapure water at 37°C for 60 minutes.

[0344] In addition, the stress mentioned above refers to the stress per unit area (mm²) 2The stress (N) was measured by clamping the test piece from both above and below the end of the test piece at a position of 8.5 mm from the end of the test piece using a tensile jig (Shimadzu Corporation, 500N screw-type flat jig), causing the test piece to be displaced until it fractured, and the maximum stress was measured (speed: 200 mm / min).

[0345] Next, the stress ratio before and after the water absorption treatment is calculated based on Equation 5 below.

[0346] <Formula 5>

[0347] Stress ratio = Stress value of the test piece after water absorption treatment / Stress value of the test piece before water absorption treatment

[0348] It should be noted that a separate silicone rubber sheet (hereinafter, sometimes referred to as Manufacturing Example 15) was prepared, and the stress and its ratio before and after the water absorption treatment were measured by the same procedure as described above. The measured values ​​are summarized in Table 3 below.

[0349]

[0350] <Evaluation of Von Mises Stress>

[0351] The von Mises stress in valve molding rings that incorporate gelatin from the gelatin sheets of Manufacturing Examples 11-14, valve molding rings that incorporate the structure of Manufacturing Example 5, and valve molding rings that incorporate polyethylene terephthalate (PET) are evaluated respectively. The specific evaluation methods are described below.

[0352] It should be noted that von Mises stress refers to stress that represents the stress state generated inside an object by a single value. It is a scalar quantity without direction and is commonly used in this field, such as product performance evaluation. Furthermore, since von Mises stress can be calculated through computer simulation, the following model of the valve-forming ring was modeled on a computer to calculate the von Mises stress.

[0353] [Model fabrication of the valve repair ring]

[0354] (1) Obtaining the S-S curve

[0355] The S-S curves (sometimes called stress-strain curves) of cobalt alloy, silicone rubber, PET cloth, gelatin cross-linked with 0.05% glutaraldehyde, gelatin cross-linked with 0.2% glutaraldehyde, gelatin cross-linked with 0.3% glutaraldehyde, and gelatin cross-linked with 0.5% glutaraldehyde were obtained with reference to JIS standards (JIS L1096:2010, JIS K6251:2017, JIS Z2241) as the constituent elements of the valve forming ring model described later (2).

[0356] The S-S curve is obtained in order to reflect the relationship between stress and strain as the inherent mechanical properties of each component, based on the implementation of the model construction described later in (2) and the implementation of the simulation-based calculation of von Mises stress.

[0357] It should be noted that for cobalt alloys (Poisson's ratio: 0.332, Young's modulus: 199, 391), silicone rubber (Poisson's ratio: 0.499, Young's modulus: 2.660), and PET fabric (Poisson's ratio: 0.499, Young's modulus: 2.947), since the obtained S-S curves show to be approximately linear, they are reflected in the model construction described later as linear materials. On the other hand, for gelatin, since the S-S curve is non-linear, it is reflected in the model construction described later after curve fitting using a hyperelastic body model (Yeoh model). This hyperelastic body model refers to the strain energy density function generally used in the analysis of hyperelastic bodies, which is known to be a model that can be approximated with high accuracy over a wide range of strain regions (e.g., Japanese Patent Application Laid-Open No. 2021-131330, Japanese Patent Application Laid-Open No. 2012-185042, etc.).

[0358] (2) Model building

[0359] Models 1 to 6 of the following valve-forming rings were manufactured. It should be noted that models 1 to 4 each incorporate the gelatin used in manufacturing examples 11 to 14 as a constituent element. Model 5 incorporates the silicone rubber sheet used in manufacturing example 15 as a constituent element. Additionally, model 6 incorporates PET fabric as a constituent element.

[0360] It should be noted that each model was built using the commercially available software Marc Mentat 2021.1.

[0361] Model 1: A cobalt alloy (0.7 mm in diameter) serves as the core of this invention; silicone rubber (2.0 mm in diameter, 0.65 mm in thickness) serves as the second layer of this invention; and PET fabric (2.4 mm in diameter, 0.2 mm in thickness) coated with gelatin (0.05% glutaraldehyde crosslinking) (2.84 mm in diameter, 0.22 mm in thickness) serves as the first layer of this invention.

[0362] Model 2: A cobalt alloy (0.7 mm in diameter) serves as the core of this invention; silicone rubber (2.0 mm in diameter, 0.65 mm in thickness) serves as the second layer of this invention; and PET fabric (2.4 mm in diameter, 0.2 mm in thickness) coated with gelatin (0.2% glutaraldehyde crosslinking) (2.84 mm in diameter, 0.22 mm in thickness) serves as the first layer of this invention.

[0363] Model 3: A cobalt alloy (0.7 mm in diameter) serves as the core of this invention; silicone rubber (2.0 mm in diameter, 0.65 mm in thickness) serves as the second layer of this invention; and PET fabric (2.4 mm in diameter, 0.2 mm in thickness) coated with gelatin (0.3% glutaraldehyde crosslinking) (2.84 mm in diameter, 0.22 mm in thickness) serves as the first layer of this invention.

[0364] Model 4: A cobalt alloy (0.7 mm in diameter) serves as the core of this invention; silicone rubber (2.0 mm in diameter, 0.65 mm in thickness) serves as the second layer of this invention; and PET fabric (2.4 mm in diameter, 0.2 mm in thickness) coated with gelatin (0.5% glutaraldehyde crosslinking) (2.84 mm in diameter, 0.22 mm in thickness) serves as the first layer of this invention.

[0365] Model 5: Cobalt alloy (0.7 mm in diameter) serves as the core of this invention; silicone rubber (2.0 mm in diameter, 0.65 mm in thickness) serves as the second layer of this invention; and PET fabric (2.4 mm in diameter, 0.2 mm in thickness) covered with silicone rubber (2.84 mm in diameter, 0.22 mm in thickness) serves as the first layer of this invention.

[0366] Model 6: Cobalt alloy (0.7mm in diameter) serves as the core of this invention, silicone rubber (2.0mm in diameter, 0.65mm in thickness) serves as the second layer of this invention, and PET cloth (2.4mm in diameter, 0.2mm in thickness) serves as the first layer of this invention.

[0367] [Calculation of Von Mises stress]

[0368] (1) Fixture

[0369] Regarding the fixture, it is considered a rigid body, and the strain of the fixture when the valve-forming ring is strained is not considered. Here, the aforementioned fixture refers to the container used in the measurement described later, which is an 8mm × 8mm × 8mm cubic container.

[0370] (2) Calculation conditions

[0371] A schematic diagram of the analytical models for calculating the von Mises stress of models 1 to 6 above is shown below. Figure 4 ( Figure 4 The model shows the valve repair ring 1, the X-axis 7, and the fixation clamp 8. In this analytical model, the von Mises stress is evaluated when the fixation part, held by the clamp, moves 2.55 mm along the X-axis (the von Mises stress was calculated using the commercially available software MarcMentat 2021.1). It should be noted that, to reduce the computational load on the computer, a similar software was used during the calculations. Figure 4The calculations are performed using a schematic diagram equivalent to a 1 / 2 symmetric model. Furthermore, since the fixture is considered a rigid body (strain of the fixture is not considered), the contact surface between the valve-forming ring and the fixture is provided with the same displacement as the fixture, instead of modeling the fixture.

[0372] In this measurement, the von Mises stress was calculated when the annulus moved 2.55 mm along the X-axis. This is based on the correspondence between the movement of the annulus along the X-axis (i.e., in-plane direction) and the movement (displacement) of the annulus by 1.7 mm (Reference: The Journal of Thoracic and Cardiovascular Surgery, Volume 122, Number 4, 666-673). Therefore, the von Mises stress required to displace it by 1.7 mm was calculated through the above calculations. The lower this value, the smaller the force exerted on the annulus for the in-plane movement, and consequently, the lower the likelihood of annulus breakage. It should be noted that in the actual calculations, as mentioned above, the value of 2.55 mm, obtained by multiplying this 1.7 mm by a safety factor of 1.5, was used.

[0373] Here, the aforementioned in-plane direction refers to Figure 3 The direction of arrow 3 in the image, as its antonym, refers to the out-of-plane direction. Figure 3 The direction of arrow 2 in the diagram.

[0374] [Calculation Results]

[0375] The von Mises stresses (maximum values) calculated based on the above are shown in Table 4. It is assumed that the location of the maximum von Mises stress, regardless of the presence or absence of gelatin, is at the fixed boundary, and is affected by the change in boundary conditions. When the fixed boundary is eliminated, the von Mises stress increases in the central part (the plane of symmetry of the analysis model).

[0376]

[0377] [Postscript]

[0378] As mentioned above, the characteristics of the von Mises stress are calculated on a computer. Since this calculation is common practice in the field, it is generally considered reliable, but its validity can also be verified from other perspectives. Verification can be performed, for example, by methods described below, but is not limited to these.

[0379] (1) Preparation in advance

[0380] Valve molding rings, such as Model 6, and identical to those in Models 1-4, were prepared. The method can be found in the description of this application. Next, marks were applied to both sides of the front end of the ring at a position of 8 mm. The cable sheath (SANWA, CA-KK22) was cut into 1.2 cm pieces. The cut cable sheaths were arranged at 10.5 mm intervals, and epoxy resin putty was filled into the cable sheaths. Then, the aforementioned valve molding rings were placed into the epoxy resin putty until they reached a position 8 mm from the front end, and left to cure overnight.

[0381] (2) Measurement

[0382] The diameter of the valve annuloplasty ring at a position 8 mm from the front end was measured using a 3D Shot (KEYENCE, VR-6000).

[0383] (3) Tensile test

[0384] Using a small benchtop testing machine (Shimadzu EZ-SX), the sample is displaced only by a specified amount of yield strain (e.g., speed: 2.5 mm / min). After displacement, the diameter at a position 8 mm from the tip is measured again using 3D shooting. Then, the strain of each valve forming ring before and after displacement is calculated. It should be noted that the specified yield strain value can be, for example, set to a value greater than or equal to the yield strain measured when calculating the aforementioned von Mises stress.

[0385] Next, the strain of the valvular annuloplasty rings of models 1-4 is compared with that of the valvular annuloplasty ring of model 6 to calculate the degree of strain. Then, the calculated result is compared with the degree of strain inferred from the above-mentioned yield strain measurement results to confirm whether the trends of the two are consistent. In this embodiment, the above verification was performed, and since the trends were consistent, the rationality of the von Mises stress calculation system was confirmed.

[0386] <Evaluation of Fatigue Failure Times>

[0387] Using the von Mises stress calculated above, and substituting it into the ELGILOY SN curve commonly used in this field (http: / / www.hightechalloys.eu / pdf / Elgiloy_Flyer.pdf), the fatigue failure number of each model is calculated as shown in Table 5.

[0388] It should be noted that the SN curve refers to the relationship between the stress repeatedly applied at a certain amplitude and the number of repetitions of the load before fracture in the fatigue failure of a material. Furthermore, the fatigue failure count refers to the number of times the sample is required to fail. Therefore, the higher the fatigue failure count, the more cycles are required for the valve repair ring to break, and thus it can be said to be more robust.

[0389]

[0390] <Summary of Evaluation Results>

[0391] According to Tables 4 and 5, by using the valve-forming rings of Models 1-4 (i.e., the gelatin used in Manufacturing Examples 11-14, where the stress ratio is 0.07-0.6) as one of their constituent elements, the von Mises stress is significantly lower compared to Models 5 and 6. That is, by using the valve-forming rings of Models 1-4, the stress applied to the valve-forming ring due to its in-plane movement is reduced (i.e., stress concentration is suppressed), thus reducing the likelihood of breakage. Specifically, comparing Models 1-3 (Manufacturing Examples 11-13) with Model 4 (Manufacturing Example 14), the von Mises stress of Models 1-3 (Manufacturing Examples 11-13) is lower. In particular, Model 1 (Manufacturing Example 11) exhibits significantly lower von Mises stress compared to the other models, making it the optimal choice from the perspective of reducing the likelihood of breakage.

[0392] Furthermore, according to Table 5, by using the valve-forming rings of Models 1-4 (i.e., valve-forming rings with stress ratios of 0.07-0.6) as one of their constituent elements, the number of fatigue failures is significantly increased compared to Models 5 and 6. That is, it can be seen that valve-forming rings using gelatin as one of their constituent elements in Models 1-4 (Manufacturing Examples 11-14) have a much lower probability of failure even with repeated use.

[0393] It should be noted that for the valve annuloplasty rings associated with models 1 to 4, it can be inferred that even if electron beam irradiation is performed as in Examples 1 to 3 above, the same results as described above will be obtained.

[0394] Industrial availability

[0395] The valvuloplasty ring of the present invention (e.g., the valvuloplasty ring of the first embodiment of the present invention) has improved hemolysis inhibition and biocompatibility compared with conventional products, and can reduce the risk of reoperation due to postoperative hemolysis. Therefore, it can be used in the production of valvuloplasty rings.

Claims

1. A valvuloplasty ring comprising: (1) a ring-shaped core, and (2) a first layer comprising a cloth or a fabric impregnated with a hydrogel, which covers a surface of the core, the hydrogel being cross-linked by irradiation.

2. The annuloplasty ring of claim 1, wherein, There is (3) a second layer comprising rubber between the core and the first layer, and a value of a ratio of an arithmetic average roughness of a surface of the first layer and not in contact with the core or the second layer to an arithmetic average roughness of a back surface of the first layer and in contact with the core or the second layer is 0.01 to 0.

40.

3. The annuloplasty ring of claim 1, wherein, The first layer comprises an impregnated layer and a hydrogel layer composed of a hydrogel, the impregnated layer comprising a cloth or a fabric impregnated with a hydrogel, and a value of a ratio of a stress applied to the hydrogel in the hydrogel layer before a water absorption treatment to a stress applied to the hydrogel after the water absorption treatment is 0.05 to 0.80, the water absorption treatment being a treatment in which the hydrogel layer is left in a solution at 30°C to 50°C for 30 minutes to 90 minutes.

4. The annuloplasty ring of any one of claims 1-3, wherein, The hydrogel is gelatin or collagen.

5. The annuloplasty ring of claim 1, wherein, The irradiation in the cross-linking by irradiation is at least one selected from the group consisting of X-ray irradiation, γ-ray irradiation, electron beam irradiation, UV irradiation, and plasma irradiation.

6. The annuloplasty ring of claim 5, wherein, The irradiation in the cross-linking by irradiation is electron beam irradiation.

7. The annuloplasty ring of claim 1, wherein, The cloth or the fabric comprises a polyester fiber.

8. The annuloplasty ring of claim 1, wherein, The hydrogel is further chemically cross-linked.

9. A valvuloplasty ring comprising: (1) a ring-shaped core, and (2) a first layer comprising a cloth or a fabric impregnated with a hydrogel, which covers a surface of the core.

10. The valvuloplasty ring according to claim 1, which is used for inhibiting hemolysis in valvuloplasty.

11. A valvuloplasty kit comprising: The valvuloplasty ring according to claim 1, and a holder and / or a gauge.

12. A method of manufacturing a valve annuloplasty ring, the valve annuloplasty ring comprising: (1) a ring-shaped core, and (2) a first layer comprising a cloth or a fabric impregnated with a hydrogel, which covers a surface of the core, the method comprising a step of irradiating the valvuloplasty ring with a radiation.

13. The method of claim 12, wherein, The step of irradiating the radiation is a step of irradiating at least one selected from the group consisting of X-rays, γ-rays, electron beams, UV, and plasma.

14. The method of claim 13, wherein, The step of irradiating the radiation is a step of irradiating an electron beam.

15. The method of claim 12, wherein, The method further comprises a step of adding a cross-linking agent.

Citation Information

Patent Citations

  • Epoxy resin composition and semiconductor device sealed therewith

    JP1988010167B2

  • Simulation method and material parameter identification method

    JP2012185042A

  • A valvuloplasty ring for receiving a replacement valve

    JP2018519895A

  • Asymmetric mitral annuloplasty band

    JP2018519986A

  • Laminate and packaging bag

    JP2020157516A